Precipitated silica and its manufacturing process

Sedimentary silica with a core/shell structure addresses dispersion and aggregation issues, enhancing the mechanical properties and homogeneity of polymer compositions.

JP2025502663APending Publication Date: 2025-01-28RHODIA OPERATIONS SAS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024535788
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-23
Filing Date
2022-12-21
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing sedimentary silica used as a reinforced filler in polymer compositions, particularly elastomer compositions, faces challenges in achieving homogeneous dispersion and high mechanical enhancement due to inefficient mixing and aggregation issues.

Method used

The development of sedimentary silica with a core/shell structure, characterized by specific surface area, particle size, and particle distribution, which enhances its dispersibility and mechanical properties when used as a filler in polymer compositions.

Benefits of technology

The sedimentary silica with a core/shell structure improves the dispersibility and mechanical properties of polymer compositions, leading to enhanced performance and homogeneity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502663000001
    Figure 2025502663000001
  • Figure 2025502663000002
    Figure 2025502663000002
  • Figure 2025502663000003
    Figure 2025502663000003
Patent Text Reader

Abstract

The present invention relates to a precipitated silica having improved dispersibility and to a process for its manufacture.The present invention further relates to the use of precipitated silica as a reinforcing filler in polymer compositions, preferably elastomeric compositions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a precipitated silica and a process for its manufacture. The present invention further relates to the use of precipitated silica as a reinforcing filler in polymer compositions, preferably elastomeric compositions. [Background technology]

[0002] The use of precipitated silica as a reinforcing filler in polymer compositions is known. In particular, the use of precipitated silica as a reinforcing filler in elastomer compositions is known. Such use is very demanding: the filler must be easily and efficiently mixed and dispersed in the elastomer composition, and must enter into chemical bonds with the elastomer, typically with a coupling agent, resulting in high and homogeneous reinforcement of the elastomer composition. In general, precipitated silica is used to improve the mechanical properties and handling and wear performance of the elastomer composition.

[0003] WO 03 / 016215 in the name of the applicant discloses precipitated silicas having certain properties concerning the so-called particle size distribution (measured by XDC or X-ray disc centrifuge) and the porosity of the primary particle aggregates. This silica works very well as reinforcement for elastomeric compositions, but the applicant has now found that in order to improve the dispersibility of such precipitated silicas in polymer compositions (which in turn improves their abrasion resistance), it is advantageous to have heterogeneous aggregates exhibiting a core / shell structure with a weak core. Summary of the Invention [Means for solving the problem]

[0004] A good dispersion in the elastomeric composition can be obtained by using precipitated silicas that are characterized by: - 40m 2 / g to 525m 2 CTAB surface areas ranging up to / g; - primary particles with an average size measured by SAXS of less than 15 nm; - the proportion of particles (by weight) with a size less than 1 μm after ultrasonic deagglomeration is at least 91%; and For a given value of the CTAB surface area, the parameter FWHM satisfies the relationship (I): |FWHM|>-0.16×|CTAB|+130(I) Particle size distribution measured by centrifugal sedimentation using CPS as defined by: DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0005] As used herein, the terms "silica" and "precipitated silica" are used synonymously.

[0006] In this specification, a numerical range defined by the expression "a to b (between a and b)" indicates a numerical range excluding the endpoints a and b. A numerical range defined by the expression "from a to b" indicates a numerical range including the endpoints a and b.

[0007] A numerical range defined by the expression "a is at least b" indicates a range in which a is equal to or greater than b.

[0008] For the avoidance of doubt, the symbol "x" in formula (I) represents a multiplication symbol, whereby the expression "a x b" means a multiplied by b. In formula (I), |CTAB| 2 This represents the CATB surface area in g / g. |CTAB| is a dimensionless number. For example, if the measured CTAB is 200m 2 / g, then |CTAB| is 200. The same applies to the other values ​​between || below, which are all dimensionless numerical values ​​of the parameters between the vertical bars.

[0009] CTAB surface area is a measure of the external specific surface area determined by measuring the amount of N-hexadecyl-N,N,N-trimethylammonium bromide adsorbed onto the silica surface at a given pH.

[0010] The CTAB surface area must be at least 40 m 2 / g, typically at least 60m 2 / g. The surface area of ​​CTAB is 70 m 2 / g. The CTAB surface area can be further increased to 110 m 2 / g, 120m 2 / g, 130m 2 / g, and in some cases even 150m 2 / g may be exceeded.

[0011] The surface area of ​​the CTAB is 525 m 2 / g, typically 300m 2 / g. The CTAB surface area is 280 m 2 / g lower than 250m 2 / g lower than 230m 2 / g, and in some cases even lower than 210m 2 / g lower than 190m 2 / g lower than 180m 2 / g or lower than 170m 2 / g.

[0012] In particular, for elastomer reinforcement applications, an advantageous range for CTAB surface area is from 50 to 300 m 2 / g, preferably 70 to 300m 2 / g, more preferably 80 to 270m 2 / g, or alternatively from 120 to 275 m2 / g. CTAB surface area is 70 m 2 / g and 250m 2 When the CTAB surface area is less than 120 m 2 / g and 230m 2 / g, more specifically, when the CTAB surface area is less than 120 m 2 / g and 180m 2Particularly good results were obtained when the solubility was lower than 1 / g.

[0013] The BET surface area of ​​the silica of the present invention is, but is not limited to, at least 10 m greater than the CTAB surface area. 2 The BET surface area is generally at least 80 m 2 / g, at least 100m 2 / g, at least 120m 2 / g, at least 140m 2 / g, at least 160m 2 / g, at least 170m 2 / g, at least 180m 2 / g, and even at least 200m 2 / g. The BET surface area is 300 m 2 / g, and even 350m 2 / g, and the BET surface also has a maximum of 260m 2 / g, up to 240m 2 / g, up to 220m 2 / g, and in some cases up to 200m 2 / g, up to 180m 2 / g or up to 170m 2 / g. In many embodiments, the BET surface area is 2 / g to 300m 2 / g.

[0014] The difference between the BET surface area and the CTAB surface area is generally taken to be representative of the microporosity of precipitated silica, in that it provides a measure of the pores in the silica that are accessible to nitrogen molecules but not to larger molecules such as N-hexadecyl-N,N,N-trimethylammonium bromide.

[0015] The precipitated silica of the present invention preferably has a particle size of at least 5 mm 2 / g, preferably at least 10m 2 The difference between the BET surface area and the CTAB surface area in g / g is preferably less than 40 m 2 / g or less, preferably 35m2 / g or less.

[0016] The silica of the present invention is essentially free of aluminum, or may even be completely free of aluminum. The silica of the present invention has an amount of aluminum below 0.50% by weight, preferably below 0.45% by weight, typically at least 0.01 and less than 0.50% by weight, preferably at least 0.01 and less than 0.45% by weight. Al or alternatively in an amount of at least 0.50 wt.%, and typically up to 3.00 wt.%, generally up to 5.00 wt.% or up to 7.00 wt.%, W Al Specific preferred aluminum range W Al is from 0.01 to less than a maximum of 0.25 wt.% (specifically, from 0.05 to less than a maximum of 0.25 wt.%), and from 0.25 to less than a maximum of 0.50 wt.% (specifically, from 0.25 to less than a maximum of 0.45 wt.%). Certain other suitable aluminum ranges W Al is from 0.50% to 1.50% by weight (specifically, from 0.50% to 1.00% by weight), and from greater than 1.50% to a maximum of 3.00% by weight. For the avoidance of doubt, the term "below" is used herein in its generally accepted and ordinary sense, i.e., "below a particular amount or level," particularly as found in Cambridge's Dictionary (online version available at https: / / dictionary.cambridge.org / dictionary / english / below), and similarly, the term "lower" is used herein in its generally accepted and ordinary sense, i.e., "located below," particularly as found in Cambridge's Dictionary, and thus the terms "below" and "lower than" have the same meaning as used herein, which is their ordinary and generally accepted meaning. Throughout the text, the amount of aluminum, W Alis defined as the weight percent amount of aluminum, meaning aluminum metal, relative to the weight of SiO2. The amount of aluminum is preferably measured using XRF wavelength dispersive X-ray fluorescence spectroscopy. This aluminum generally comes at least in part from the raw material. In some embodiments, an aluminum compound (such as sodium aluminate) is added during the synthesis of the precipitated silica and / or during the liquefaction process as described below.

[0017] The silica of the present invention may contain elements, non-limiting examples of which are, for example, Al, Ga, B, Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Fe, Co, Mg, Ca or Zn. Thus, in one embodiment, the silica of the present invention contains at least one element selected from Al, Ga, B, Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Fe, Co, Mg, Ca or Zn, and specifically, the silica of the present invention may contain Al and at least one element selected from Ga, B, Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Fe, Co, Mg, Ca and Zn.

[0018] The precipitated silica of the present invention is further characterized by a broad particle size distribution and small size of primary particles. The term particle is used to refer to the smallest aggregates of primary silica particles that can be broken by mechanical action. In other words, the term "particle" refers to a collection / agglomerate of indivisible primary particles, the aggregates being characterized by their claimed FWHM, while the indivisible primary particles are characterized by their claimed average size. The aggregates preferably have a core / shell structure. Advantageously, the core is composed of larger primary particles than the shell, and therefore the core is more fragile.

[0019] The precipitated silica according to the invention has a size d measured by SAXS (small angle X-ray scattering as described below) of less than 15 nm, preferably less than 14 nm, more preferably less than 13 nm. ZSGenerally, the size of the primary particles is greater than 4 nm, preferably greater than 5 nm, and more preferably greater than 6 nm. ZS Particular suitable ranges for are 5-15 nm, preferably 6-14 nm, possibly 6-13 nm, 7-13 nm, 6-12 nm, 7-12 nm, 6-11 nm, 7-11 nm, 6-10 nm or 7-10 nm. Typically, the primary particles of silica according to the invention all have a particle size in the same range (generally 5-15 nm, preferably 6-14 nm, more preferably 5-11 nm and even more preferably 6-10 nm), which refers to the fact that there is one population of primary particles.

[0020] The L of the precipitated silica according to the invention d is typically at least 1.00, preferably at least 1.25, and more preferably at least 1.50. d The L of the silica of the present invention is generally below 2.10, typically below 2.00. d is preferably 1.00 to 2.00, more preferably 1.50 to 1.90. d is defined as follows: d =(d 84 -d 16 ) / d 50 , where dn is the particle diameter below which n% of the total measured mass falls. d is a dimensionless number calculated on the cumulative particle size curve.

[0021] To characterize the particle size distribution width of the precipitated silica according to the invention, the parameter FWHM is used, determined by centrifugal sedimentation in a disk centrifuge, using the CPS detailed below. The FWHM (or full width at half maximum) is obtained from the CPS curve. The FWHM measures the distribution width of the silica objects around the average size defined by the mode (in nm). If the FWHM is large around the average value, the silica product is inhomogeneous. If the FWHM is sharp around the average value, the silica product is more homogeneous. In the case of a Gaussian particle size distribution (which is rarely the case in practice), the parameter FWHM is determined by the parameter L d Correlated with.

[0022] The FWHM of the precipitated silica according to the invention is generally at least 80, frequently at least 90, often at least 100 and sometimes at least 110. In addition, the parameter FWHM is generally at most 300, frequently at most 250, often at most 200, sometimes at most 190, at most 180, at most 170 or at most 160. Good results have been obtained with an FWHM in the range from 100 to 250.

[0023] As mentioned above, the parameter FWHM of the precipitated silica according to the invention obeys the relationship (I): |FWHM|>-0.16×|CTAB|+130(I) In some cases, the parameter FWHM of the precipitated silica according to the invention obeys the relationship (I1): |FWHM|>k1×-0.16×|CTAB|+130(I1) where k1 is a dimensionless number equal to 1.20.

[0024] In addition, the parameter FWHM of the precipitated silica according to the invention generally obeys the relationship (I2): |FWHM| <k2×-0.16×|CTAB|+130(I2) where k2 is a dimensionless number equal to 3.00. In many cases, the parameter FWHM of the precipitated silica according to the invention obeys the relationship (I3): |FWHM| <k3×-0.16×|CTAB|+130(I3) where k3 is a dimensionless number equal to 2.20. Sometimes, the parameter FWHM of the precipitated silica according to the invention obeys the relationship (I4): |FWHM| <k4×-0.16×|CTAB|+130(I4) where k4 is a dimensionless number equal to 1.80.

[0025] The FWHM of the precipitated silica according to the invention may be in accordance with the relationships (I) and (I2). It may also be in accordance with the relationships (I) and (I3). It may also be in accordance with the relationships (I) and (I4). It may also be in accordance with the relationships (I1) and (I2). It may also be in accordance with the relationships (I1) and (I3). It may also be in accordance with the relationships (I1) and (I4).

[0026] The precipitated silica according to the invention 50 is determined by centrifugal sedimentation in a disk centrifuge using a CPS, as detailed below. 50 represents the particle diameter below (and above) that found for 50% of the total mass of particles. Therefore, d 50 represents the median particle size of a given distribution, and in this context the term "size" is intended to mean "diameter".

[0027] The silica of the present invention 50 is preferably characterized by the following formula: |d 50 |>-0.81×|CTAB|+263. Typically, this d 50 is comprised between 110 nm and 240 nm, preferably between 130 and 220 nm.

[0028] The silica of the present invention 84 is preferably characterized by the following formula: |d 84 |<2.81×|FWHM|+35. Typically, this d84 is comprised between 200 and 550 nm, preferably between 250 and 500 nm.

[0029] The fines fraction (τf), the so-called fraction (by weight) of particles less than 1 μm in size after ultrasonic deagglomeration (determined by the "sedigraph" test method described below), is also a way of illustrating the capacity for dispersion of the precipitated silica according to the invention. According to the invention, τf is at least 91%. In a preferred embodiment, this fines fraction τf is at least 92%. The fines fraction τf is more preferably at least 94%, even more preferably at least 95%, and in some particularly preferred embodiments, τf may be at least 96%, at least 97%, at least 98%, or at least 99%. In many cases, τf is at most 99%, and sometimes it is at most 98%. Particular preferred ranges for the fines fraction τf are from 95% to 99% and from 96% to 99%. It is understood that these values ​​can be applied to any precipitated silica, regardless of its form. They can be applied in particular to non-granulated products, i.e. powders or micropearls. They can also be applied to granules.

[0030] Precisely, the form of the precipitated silica of the present invention is not particularly limited. Thus, the silica of the present invention may be in a form selected from, inter alia, powder, substantially spherical beads (commonly referred to as "micropearls"), granules and mixtures thereof. In some embodiments, it is in the form of a powder. In some other embodiments, it is in the form of micropearls. In still other embodiments, it is in the form of granules.

[0031] A second object of the present invention is a process for preparing precipitated silica, the process comprising the steps of: (i) providing a starting solution having a pH of from 2.00 to 5.50; (ii) simultaneously adding a silicate and an acid to the starting solution so as to maintain the pH of the reaction medium in the range of from 2.00 to 5.50; (iii) stopping the addition of acid and silicate and adding a base to the reaction medium to increase the pH of the reaction medium to a value between 7.00 and 10.00; (iv) simultaneously adding a silicate and an acid to the reaction medium so as to maintain the pH of the reaction medium in the range of from 7.00 to 10.00; (v) continuing the addition of acid to the reaction medium while stopping the addition of silicate to reach a pH of the reaction medium below 6.00 to obtain a suspension of precipitated silica; Step (i) comprises the steps of: (ia) finally preparing an aqueous medium containing electrolyte as an initial stock; (ib) adding silicate and acid simultaneously to the aqueous medium such that the pH of the aqueous medium is maintained in the range of from 7.00 to 10.00, the amount of silicate added to the aqueous medium being 1-10% of the total amount of silicate required for the reaction, preferably 5-9% of the total amount of silicate required for the reaction; (ic) stopping the addition of silicate while continuing the addition of acid to the aqueous medium obtained in step (ib) to provide a starting solution having a pH of from 2.00 to 5.50.

[0032] Said process is particularly well suited for preparing the precipitated silica of the first object. Thus, said second object of the invention is advantageously a process for preparing the precipitated silica of the first object, said process comprising: (i) providing a starting solution having a pH of from 2.00 to 5.50; (ii) simultaneously adding a silicate and an acid to the starting solution so as to maintain the pH of the reaction medium in the range of from 2.00 to 5.50; (iii) stopping the addition of acid and silicate and adding a base to the reaction medium to increase the pH of the reaction medium to a value between 7.00 and 10.00; (iv) simultaneously adding a silicate and an acid to the reaction medium so as to maintain the pH of the reaction medium in the range of from 7.00 to 10.00; (v) continuing the addition of acid to the reaction medium while stopping the addition of silicate to reach a pH of the reaction medium below 6.00 to obtain a suspension of precipitated silica; Step (i) comprises the steps of: (ia) finally preparing an aqueous medium containing electrolyte as an initial stock; (ib) adding silicate and acid simultaneously to the aqueous medium such that the pH of the aqueous medium is maintained in the range of from 7.00 to 10.00, the amount of silicate added to the aqueous medium being 1-10% of the total amount of silicate required for the reaction, preferably 5-9% of the total amount of silicate required for the reaction; (ic) stopping the addition of silicate while continuing the addition of acid to the aqueous medium obtained in step (ib) to provide a starting solution having a pH of from 2.00 to 5.50.

[0033] The total amount of silicate to obtain a given final amount of silica can be determined by the person skilled in the art at the beginning of the process according to common general knowledge. The amount of silicate added in step (ib) is denoted hereinafter as AS0 silicate ratio.

[0034] The term "base" is used herein to mean one or more bases that may be added during the process of the present invention, which includes the group consisting of silicates as defined below. Any base may be used in the process. In the addition of silicates, notable non-limiting examples of suitable bases are, for example, alkali metal hydroxides and ammonia. Preferably, the base is a silicate, more preferably the same silicate as that used in the process.

[0035] The term "silicate" is used herein to refer to one or more silicates that may be added during the course of the process of the present invention. The silicate is typically selected from the group consisting of alkali metal silicates. The silicate is advantageously selected from the group consisting of sodium silicate and potassium silicate. The silicate may be in any known form, such as metasilicate or disilicate. It may be sourced from a variety of materials, such as sand, natural sources containing silica, combustion products (RHA or rice husk ash) or the like, or even waste products (from construction waste, mining waste, etc.).

[0036] If sodium silicate is used, the latter generally has a SiO2 / Na2O weight ratio of from 2.0 to 4.0, in particular from 2.4 to 3.9, for example from 3.1 to 3.8.

[0037] The silicate may have a concentration (expressed in terms of SiO2) of from 3.9% to 25.0% by weight, for example from 5.6% to 23.0% by weight, particularly from 5.6% to 21.0% by weight.

[0038] The term "acid" is used herein to refer to one or more acids that may be added during the course of the process of the present invention. Any acid may be used during the process. Typically, mineral acids such as sulfuric acid, nitric acid, phosphoric acid or hydrochloric acid, or organic acids such as carboxylic acids, e.g., acetic acid, formic acid or carbonic acid, are used. Good results have been obtained with sulfuric acid.

[0039] The acid can be metered into the reaction medium in dilute or concentrated form. Different concentrations of the same acid can be used at different stages of the process. Preferably, dilute acid is used until the gel point is reached (this occurs during step (ii)) and concentrated acid is used after the gel point is reached. Preferably, the dilute acid is dilute sulfuric acid (i.e. having a concentration much lower than 80% by weight, preferably less than 20% by weight, generally less than 14% by weight, in particular less than or equal to 10% by weight, for example between 5% and 10% by weight). Advantageously, the concentrated acid is concentrated sulfuric acid, i.e. having a concentration of at least 80% by weight (and generally less than or equal to 98% by weight), preferably at least 90% by weight; in particular, the concentration is between 90% and 98% by weight, for example between 91% and 97% by weight.

[0040] In a preferred embodiment of the process, sulfuric acid and sodium silicate are used at all stages of the process. The same sodium silicate, preferably sodium silicate having the same concentration expressed as SiO2, is used at all stages of the process.

[0041] In step (i) of the process, a starting solution having a pH of from 2.00 to 5.00 is provided in the reaction vessel. Preferably, the starting solution has a pH of from 2.50 to 5.00, in particular from 3.00 to 4.50, for example the pH is from 3.50 to 4.50.

[0042] According to the invention, this starting solution is prepared as described above, ie using the following steps (ia) to (ic).

[0043] Without being bound by theory, the Applicant believes that during these sub-steps of step (i), larger primary particles are generated than those generated in the subsequent steps of the process (i.e. in steps (ii) and (iv)), which makes it possible to arrive at heterogeneous agglomerates with a large particle size distribution.

[0044] The starting solution of step (i) may or may not contain an electrolyte. Preferably, the starting solution of step (i) contains an electrolyte to aid in recycling the water stream in the process.

[0045] The term "electrolyte" is used herein in its generally accepted sense, i.e. to identify any ionic or molecular substance that, when in solution, decomposes or dissociates to form ions or charged particles. The term "electrolyte" is used herein to indicate that one or more electrolytes may be present. Electrolytes such as salts of alkali metals and alkaline earth metals may be mentioned. Advantageously, the electrolyte used in the starting solution is a salt of the metal and acid of the starting silicate used in the process. Notable examples are, for example, sodium chloride in the case of the reaction of sodium silicate with hydrochloric acid or, preferably, sodium sulfate in the case of the reaction of sodium silicate with sulfuric acid. Preferably, the electrolyte does not contain aluminum.

[0046] Preferably, when sodium sulfate is used as electrolyte in step (i), its concentration in the starting solution is from 5 to 40 g / L, in particular from 8 to 30 g / L, for example from 10 to 25 g / L.

[0047] Step (ii) of the process involves the simultaneous addition of an acid and a silicate to the starting solution. The rates of addition of the acid and the silicate during step (ii) are controlled so as to maintain the pH of the reaction medium in the range of from 2.00 to 5.50. The pH of the reaction medium is preferably maintained in the range of from 2.50 to 5.00, in particular from 3.00 to 5.00, for example from 3.20 to 4.80.

[0048] The simultaneous addition in step (ii) is advantageously carried out in such a way that the pH value of the reaction medium is always equal (to within ±0.20 pH units) to the pH reached at the end of step (i).

[0049] Preferably, step (ii) consists of the simultaneous addition of acid and silicate as detailed above. Generally, the gel point is reached during step (ii). In one embodiment, the amount of silicate added in step (ii) after the gel point is reached is between 5% and 55% of the total amount of silicate added during step (ii), preferably between 10% and 50%, more preferably between 15% and 45% of the total amount of silicate added during step (ii). The gel point is defined as the point at which the reaction medium undergoes a sudden change in viscosity that can be determined by measuring the torque on the stirrer. Generally, the stirring torque increases by a value between 20% and 60% compared to the torque value before the gel point, preferably by a value between 25% and 55%, more preferably by a value between 30% and 50% compared to the torque value before the gel point.

[0050] Then, in step (iii), the addition of acid and silicate is stopped and a base is added to the reaction medium, the addition of the base being stopped when the pH of the reaction medium reaches a value between 7.00 and 10.00, preferably between 7.50 and 9.50.

[0051] In a first embodiment of the process the base is a silicate. Thus, in step (iii), the addition of the acid is stopped whilst the addition of the silicate to the reaction medium is continued until a pH of from 7.00 to 10.00, preferably from 7.50 to 9.50, is reached.

[0052] In a second embodiment of the process, the base is different from the silicate and is selected from the group consisting of alkali metal hydroxides, preferably sodium or potassium hydroxide. When sodium silicate is used in the process, the preferred base may be sodium hydroxide.

[0053] Thus, in this second embodiment of the process, in step (iii), the addition of acid and silicate is stopped and a base different from the silicate is added to the reaction medium until a pH of from 7.00 to 10.00, preferably from 7.50 to 9.50, is reached.

[0054] That is, it may be advantageous to carry out, at the end of step (iii), a maturation step of the reaction medium, after stopping the addition of the base. This step is preferably carried out at the pH obtained at the end of step (iii). The maturation step may be carried out whilst stirring the reaction medium. It is preferably carried out for a period of between 2 and 45 minutes, in particular between 5 and 25 minutes, whilst stirring the reaction medium. The maturation step preferably does not involve the addition of any acid or silicate.

[0055] After step (iii) and the optional maturation step, simultaneous addition of acid and silicate is carried out so as to maintain the pH of the reaction medium in the range of from 7.00 to 10.00, preferably from 7.50 to 9.50.

[0056] The simultaneous addition of acid and silicate (step (iv)) is typically carried out so that the pH value of the reaction medium is maintained equal (to within ±0.20 pH units) to the pH reached at the end of the previous step, i.e. step (iii).

[0057] Preferably, the amount of silicate added to the reaction medium during step (iv) is at least 45% of the total amount of silicate required for the reaction.

[0058] It should be noted that the process of the present invention may include further steps. For example, an acid may be added to the reaction medium between steps (iii) and (iv), in particular between the optional maturation step after step (iii) and step (iv). The pH of the reaction medium after this addition of acid should remain in the range of 7.00 to 9.50, preferably 7.50 to 9.50.

[0059] In step (v), the addition of silicate is stopped while continuing the addition of acid to the reaction medium to obtain a pH value in the reaction medium of less than 6.00, preferably between 3.00 and 5.50, in particular between 3.00 and 5.00, and a suspension of precipitated silica is obtained in the reaction vessel.

[0060] At the end of step (v), and therefore after the addition of acid to the reaction medium has been stopped, an ageing step can advantageously be carried out, which can be carried out at the same pH obtained at the end of step (v) and under the same time conditions as those described above for the ageing step that can optionally be carried out between steps (iii) and (iv) of the process.

[0061] The reaction vessel in which the entire reaction between the silicate and the acid is carried out is usually equipped with suitable stirring and heating devices.

[0062] The entire reaction of the silicate with the acid (steps (i) to (v)) is generally carried out at a temperature of from 40 to 97°C, in particular from 60 to 95°C, preferably from 80 to 95°C, more preferably from 85 to 95°C.

[0063] According to one variant of the invention, the overall reaction of silicate with acid is carried out at a constant temperature, usually from 40 to 97°C, in particular from 80 to 95°C, and even more particularly from 85 to 95°C.

[0064] According to another variant of the invention, the temperature at the end of the reaction is higher than the temperature at the beginning of the reaction; therefore, the temperature at the beginning of the reaction (e.g. during steps (i) to (iii)) is preferably maintained in the range of from 40 to 85° C., the temperature is then preferably raised to a value in the range of from 80 to 95° C., further from 85 to 95° C., and it is maintained at that value until the end of the reaction (e.g. during steps (iv) and (v)).

[0065] At the end of the step just described, a suspension of precipitated silica is obtained which is subsequently separated (liquid / solid separation). The process typically comprises a further step (vi) of filtering the suspension and drying the precipitated silica.

[0066] The separation carried out in the preparation process according to the invention usually involves a filtration, if necessary followed by washing, which is carried out according to any suitable method, for example by means of a belt filter, a rotary filter, for example a vacuum filter or preferably a filter press.

[0067] The filter cake is then subjected to a liquefaction operation. The term "liquefaction" is intended herein to indicate the process by which a solid, i.e., the filter cake, is converted into a fluid-like mass, generally by adding a liquid thereto. After the liquefaction step, the filter cake is in a flowable, fluid-like form and the precipitated silica is in suspension.

[0068] The liquefaction step may include mechanical treatment that results in a reduction in the particle size distribution of the suspended silica. The mechanical treatment may be carried out by passing the filter cake through a high shear mixer, a colloid type mill or a ball mill. Alternatively, the liquefaction step may be carried out by subjecting the filter cake to chemical action, for example by the addition of an acid or an aluminum compound, such as sodium aluminate. Alternatively, the liquefaction step may include both mechanical and chemical action.

[0069] The suspension of precipitated silica obtained after the optional liquefaction step is finally treated with additional chemicals, such as, for example, organic chemicals (for example, polycarboxylic acids), and then preferably dried.

[0070] This drying can be carried out according to the techniques known in the art.Preferably, drying is carried out by spraying.For this purpose, any type of suitable atomizer can be used, in particular turbine, nozzle, liquid pressure or two-fluid spray dryer.Generally, when filtration is carried out using a filter press, a nozzle type atomizer is used, and when filtration is carried out using a vacuum filter, a turbine type atomizer is used.

[0071] When the drying operation is carried out using a nozzle spray dryer, the precipitated silica obtained is usually in the form of substantially spherical beads, commonly called "micropearls". After this drying operation, the recovered product can optionally undergo a grinding or pulverization step, and the precipitated silica obtained is generally in the form of a powder. After this drying operation, the recovered micropearls can optionally undergo a step in which they undergo an agglomeration step, which can consist, for example, of direct compression, wet granulation, extrusion or, preferably, dry compression, and the precipitated silica obtained is then generally in the form of granules.

[0072] If the drying operation is carried out by means of a turbine spray dryer, the precipitated silica obtainable then may be in the form of a powder.

[0073] In one embodiment of the present invention, the filter cake is not sent to a liquefaction step, but is directly dried by centrifugal flash drying (eg, by a Hosokawa-type process).

[0074] Finally, the product dried, ground or pulverized as indicated above may optionally be subjected to an agglomeration step, which consists, for example, of direct compression, wet granulation (i.e. using water, a binder such as a silica suspension), extrusion or preferably dry compaction.

[0075] The precipitated silica obtainable by this agglomeration process is generally in the form of granules.

[0076] The precipitated silicas of the invention can be used in many applications, such as catalysts, catalyst supports, absorbents for active materials (particularly carriers for liquids used in foods, such as vitamins (vitamin E or choline chloride)), viscosity modifiers, anti-blocking or anti-caking agents, or as additives for toothpaste, concrete or paper. They can also be advantageously used in the manufacture of thermal insulation materials or in the preparation of resorcinol-formaldehyde / silica composites. The precipitated silicas of the invention find a particularly advantageous application as fillers in polymeric compositions.

[0077] Further objects of the present invention are therefore (i) the use of the silica of the invention as defined above for the manufacture of a filled polymer composition, and (ii) a composition comprising the silica of the invention as defined above and at least one polymer. When referring to the polymers in the composition, the phrase "at least one" is used herein to indicate that one or more polymers of each type can be present in the composition.

[0078] The expression "copolymer" is used herein to refer to a polymer that includes repeat units derived from at least two monomeric units of different nature.

[0079] The at least one polymer may be chosen from among thermosetting and thermoplastic polymers, the latter being preferred.

[0080] Notable non-limiting examples of suitable thermoplastic polymers include polystyrene, styrenic polymers such as (meth)acrylic acid ester / styrene copolymers, acrylonitrile / styrene copolymers, styrene / maleic anhydride copolymers, ABS, and the like; acrylic polymers such as polymethyl methacrylate, polycarbonates, polyamides, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyphenylene ethers, polysulfones, polyaryletherketones, polyphenylene sulfides, thermoplastic polyurethanes, polyethylene, polypropylene, polybutene, poly-4-methylpentene, polyolefins such as ethylene / propylene copolymers, ethylene / α-olefin copolymers, copolymers of α-olefins with various monomers, for example ethylene / vinyl acetate copolymers, ethylene / (meth)acrylic acid ester copolymers, ethylene / maleic anhydride copolymers, ethylene / acrylic acid copolymers, polylactic acid, polycaprolactones, and aliphatic polyesters such as aliphatic glycol / aliphatic dicarboxylic acid copolymers.

[0081] The silica of the invention can be advantageously used as a reinforcing filler in elastomer compositions.A preferred object of the invention is therefore a composition comprising the silica of the invention and one or more elastomers, preferably exhibiting at least one glass transition temperature between -150°C and +300°C, for example between -150°C and +20°C.

[0082] Notable non-limiting examples of suitable elastomers are diene elastomers. For example, elastomers derived from aliphatic or aromatic monomers containing at least one unsaturation, such as ethylene, propylene, butadiene, isoprene, styrene, acrylonitrile, isobutylene or vinyl acetate, polybutyl acrylate or mixtures thereof, among others, can be used. Mention can also be made of functionalized elastomers, which are elastomers functionalized by chemical groups located along the polymer chain and / or at one or more ends thereof (e.g., by functional groups capable of reacting with the surface of silica) and halogenated polymers. Mention can also be made of polyamides, ethylene homo- and copolymers, propylene homo- and copolymers.

[0083] Among the diene elastomers, mention may be made, for example, of polybutadiene (BR), polyisoprene (IR), butadiene copolymers, isoprene copolymers or mixtures thereof, in particular styrene / butadiene copolymers (SBR, in particular ESBR (emulsion) or SSBR (solution)), isoprene / butadiene copolymers (BIR), isoprene / styrene copolymers (SIR), isoprene / butadiene / styrene copolymers (SBIR), ethylene / propylene / diene terpolymers (EPDM) and also related functionalized polymers (presenting pendant polar groups or polar groups at the chain ends, capable of interacting, for example, with silica).

[0084] Mention may also be made of natural rubber (NR) and epoxidized natural rubber (ENR).

[0085] The polymeric compositions may be sulfur vulcanized or specifically crosslinked with peroxides or other crosslinking systems such as diamines or phenolic resins.

[0086] Generally, the polymer composition further comprises at least one (silica / polymer) coupling agent and / or at least one coating agent, which may further comprise, inter alia, an antioxidant.

[0087] Non-limiting examples of suitable coupling agents are, for example, "symmetric" or "asymmetric" silane polysulfides. More specifically, bis((C1-C4)alkoxyl(C1-C4)alkylsilyl(C1-C4)alkyl) polysulfides (specifically disulfides, trisulfides or tetrasulfides), such as bis(3-(trimethoxysilyl)propyl) polysulfides or bis(3-(triethoxysilyl)propyl) polysulfides, such as triethoxysilylpropyl tetrasulfide, may be mentioned. Monoethoxydimethylsilylpropyl tetrasulfide may also be mentioned. Silanes containing masked or free thiol functions of mercaptopropyltriethoxysilane (such as NXT™ or NXT™ Z45 silane), and mixtures mercaptopropyltriethoxysilane+octyltriethoxysilane (such as SI 363™ from Evonik) may also be mentioned.

[0088] The coupling agent can be pre-grafted to the polymer. It can also be used in the free state (i.e. not pre-grafted) or grafted on the surface of the silica. The same applies to the optional coating agent. If, after drying, a coupling agent is added to the silica (i.e. grafted to it), it is generally an ethoxy- or chloro-silane.

[0089] The coupling agent may optionally be combined with a suitable "coupling activator", ie a compound that is mixed with the coupling agent to increase the effectiveness of the latter.

[0090] The weight ratio of the silica of the invention in the polymer composition can vary in a fairly wide range. It usually represents from 1% to 250%, particularly from 5% to 200%, particularly from 10% to 170%, for example from 20% to 140% or even from 25% to 130%, or alternatively from 10% to 40%, relative to the amount of polymer. This percentage is therefore sometimes referred to as phr or parts per hundred rubber in the case of elastomeric compositions.

[0091] The silica according to the invention may advantageously constitute all of the reinforcing inorganic filler and even all of the reinforcing filler of the polymer composition.

[0092] The silica of the invention can optionally be combined with at least one other reinforcing filler, for example a conventional or highly disperse silica such as Zeosil® Premium SW, Zeosil® Premium 200MP, Zeosil® 1165MP, Zeosil® 1115MP or Zeosil® 1085 GR (available from Solvay), or another reinforcing inorganic filler such as nanoclay, alumina, etc. Alternatively, the silica of the invention may be combined with an organic reinforcing filler such as carbon black nanotubes, graphene, starch, cellulose, etc.

[0093] The silica according to the invention then preferably constitutes at least 30% by weight, preferably at least 60% and indeed even at least 80% by weight, of the total amount of reinforcing fillers.

[0094] Further optional components of the formulation include accelerators (such as CBS, MBTS, TBzTD and DPG), crosslinkers (such as peroxides or sulfur), process oils, resins (terpenes and C5 resins, notably those commercially available as Wingtack™ or as Dercolyte™), oligomers of SBR, BR or IR, activators (stearic acid and / or zinc oxide), processing aids (fatty acids, zinc soaps and PEG), waxes acting as protectants (e.g., PE wax), antioxidants, UV protection agents and antiozonants (such as 6PPD and TMQ).

[0095] The silica of the present invention is characterized by its outstanding ability to disperse in elastomer compositions. A known method for determining the ability of a filler to disperse in an elastomer matrix is ​​described in S.Otto et al., Kautschuk Gummi Kunststoffe, 58 Jahrgang, NR 7-8 / 2005. This method, described in more detail below, relies on optical analysis and defines the dispersion of the filler in the elastomer matrix with a Z value that is proportional to the amount of undispersed filler in the matrix, with 100 indicating a perfect mix and 0 indicating a poor mix.

[0096] The silicas of the present invention, when dispersed in an elastomeric matrix, are characterized by Z values ​​that are typically higher than those of comparable mixtures containing prior art silicas.

[0097] The composition comprising the precipitated silica of the present invention can be used for the manufacture of many articles.The composition comprising the precipitated silica of the present invention may be used in many articles.Non-limiting examples of the finished products comprising at least one of the above polymer compositions are, for example, footwear soles, floor coverings, gas barriers, flame retardant materials, and rollers for cableways, seals for household appliances, seals for liquid or gas pipes, brake system seals, pipes (plastic), coating materials (particularly cable coating materials), cables, engine supports, battery separators, conveyor belts, transmission belts or tire parts, for example tire treads, the latter being preferred. Furthermore, many embodiments of the present invention relate to finished products other than any part of a tire, other than any tire, and other than any article constituting a tire, which consist of or comprise at least one portion consisting of a composition comprising (i) the precipitated silica of the present invention and (ii) at least one polymer, and optionally one or more elastomers, and which may be selected from the group consisting of soles of footwear, floor coverings, engineering components (rollers for cableways), seals (seals for household appliances, seals for liquid or gas pipes, and brake system seals), pipes (especially plastic pipes), coating materials (particularly cable coating materials), cables, supports (especially engine supports), separators (especially battery separators), and belts (conveyor belts and transmission belts).

[0098] As mentioned above, the precipitated silica of the present invention is present in an amount W of less than 0.50% by weight, preferably less than 0.45% by weight, typically at least 0.01 and less than 0.50% by weight, preferably at least 0.01 and 0.45% by weight. Al The specific preferred range of aluminum is W Alis from 0.01 to less than a maximum of 0.25% by weight (specifically, from 0.05% to less than a maximum of 0.25% by weight), and from 0.25% to less than a maximum of 0.50% by weight (specifically, from 0.25% to less than a maximum of 0.45% by weight and from 0.45% to less than a maximum of 50% by weight).

[0099] Amount W below 0.50% by weight Al The precipitated silica of the present invention containing aluminum at 0.50% by weight can be used in any one of the above-mentioned applications. Al The precipitated silicas of the present invention containing aluminum at 0.50% by weight can be advantageously utilized as fillers in polymer compositions, in particular as reinforcing fillers in elastomeric compositions. It is therefore a preferred object of the present invention to provide a method for the preparation of precipitated silicas containing aluminum at 0.50% by weight or less. Al Compositions comprising the present invention's precipitated silica containing aluminum in an amount W below 0.50% by weight and at least one polymer, in particular Al The present invention relates to a composition comprising the present precipitated silica containing aluminum at 0.50% by weight and one or more elastomers. The nature of the at least one polymer, in particular the nature of the elastomer, may be as detailed above. The composition may additionally comprise at least one (silica / polymer) coupling agent and / or at least one coating material, which may also comprise one or more other additives such as those detailed above. In the polymer composition, in particular in the elastomer composition, an amount W below 0.50% by weight may be used. Al The proportion by weight of the precipitated silica of the invention containing aluminium may be as detailed above.

[0100] Amount W below 0.50% by weight Al The precipitated silica of the present invention containing aluminum at 0.50% by weight may be used for the manufacture of any one of the above-specified articles. Al The precipitated silica of the present invention containing aluminum at 0.50% by weight may be used in any one of the above-specified articles. AlA preferred use of the precipitated silica of the invention containing aluminum at 0.50% by weight is for the manufacture of one or more parts of a tire, for example for the manufacture of a tire tread. Another preferred use thereof is in a part of a tire, for example in a tire tread. Thus, a preferred object of the present invention is to (i) obtain a precipitated silica containing aluminum at 0.50% by weight or less in an amount W of 0.50% by weight or less. Al and (ii) at least one polymer, preferably (i) in an amount W of less than 0.50 wt. %. Al A highly preferred object of the present invention is to provide a tire component comprising a composition comprising the present precipitated silica containing aluminum in an amount W of less than 0.50% by weight. Al and (ii) at least one polymer. Al and (ii) one or more elastomers. A related object of the present invention is a tire comprising this part, in particular a tire comprising this tread, and another related object of the present invention is an article comprising a tire comprising this part, generally a vehicle, in particular an automotive vehicle (e.g. a car, a van, a mobile home, a bus, a coach, a truck, a construction machine such as a backhoe loader or a dump truck), and possibly also a non-automotive vehicle (such as a trailer or a cart). The nature of the at least one polymer, in particular the nature of the elastomer, may be as detailed above. The composition may additionally comprise at least one (silica / polymer) coupling agent and / or at least one coating material, which may also comprise one or more other additives, such as those detailed above. An amount W of less than 0.50% by weight in the polymer composition (in particular the elastomeric composition) comprised in the tire part (e.g. the tire tread) may be less than 0.50% by weight. Al The proportion by weight of the precipitated silica of the invention containing aluminium may be as detailed above.

[0101] As also indicated above, the precipitated silica of the present invention may alternatively be present in an amount W of at least 0.50 wt. % and typically up to 3.00 wt. %. Al Certain other suitable aluminum ranges W Al is from 0.50 wt % to 1.50 wt % (specifically, from 0.50 wt % to 1.00 wt %), and from greater than 1.50 wt % up to 3.00 wt %.

[0102] An amount W of at least 0.50% by weight Al The precipitated silica of the invention containing aluminum in an amount of at least 0.50% by weight may be used as a catalyst, a catalyst support, an absorbent for active materials (specifically a support for oligomers and process oils, etc.), as a viscosity modifier, an antiblocking or anticaking agent, or as an additive for concrete or paper. Al The precipitated silica of the invention containing aluminum at 0.50% by weight may also be used in the manufacture of thermal insulation materials or in the preparation of resorcinol-formaldehyde / silica composites. Al The precipitated silicas of the invention containing aluminium at 100° C. may also be used as fillers in polymer compositions.

[0103] An amount W of at least 0.50% by weight Al The precipitated silica of the present invention containing aluminum at 0.50 wt. % may be used for the manufacture of finished articles other than tire parts, other than tires, and other than articles including tires, which may contain at least one of the polymer compositions described above. Al The precipitated silica of the invention containing aluminum in an amount W of at least 0.50% by weight may be used in finished products other than tire parts, other than tires and other than articles containing tires, which finished products may contain at least one of the polymer compositions described above. Thus, the object of the invention is finished products other than any part of a tire, other than any tire and other than any article containing a tire, which finished products contain at least one of the polymer compositions described above. AlThe composition may be made up of or may comprise at least one part consisting of a composition comprising the precipitated silica of the invention containing aluminum at 0° C. and (ii) at least one polymer, and optionally one or more elastomers. The finished article other than any part of a tire, other than any tire, and other than any article including a tire, may be selected from the group consisting of footwear soles, floor coverings, engineering components (rollers for cableways), seals (seals for household appliances, seals for liquid or gas pipes, and brake system seals), pipes (particularly plastic pipes), coating materials (particularly cable coating materials), cables, supports (particularly engine supports), separators (particularly battery separators), and belts (conveyor belts and transmission belts). The nature of the at least one polymer, and optionally the nature of the elastomer, may be as detailed above. The composition may additionally comprise at least one (silica / polymer) coupling agent and / or at least one coating material, which may also comprise one or more other additives, such as those detailed above. An amount W of at least 0.50% by weight in the polymer composition (and optionally in the elastomeric composition) contained in any finished article other than any part of a tire other than a tire and any article other than a tire. Al The proportion by weight of the precipitated silica of the invention containing aluminium may be as detailed above.

[0104] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements in this application to the extent that any term may be unclear, the statements herein shall control.

[0105] Analysis method The physicochemical properties of the precipitated silica of the invention were determined using the methods described below.

[0106] Possible pretreatment of precipitated silica. When the precipitated silica is in the form of highly aggregated particles, typically when the precipitated silica is in a form other than a powder, pretreatment thereof is desirable before applying certain analytical methods, such as a method for determining the CTAB surface area and / or a method for determining the primary particle size by SAXS (both methods of interest are detailed herein below).

[0107] In particular, on the one hand, when the precipitated silica is in the form of micropearls, in other words in the form of a primary form of highly aggregated particles, it is desirable to deagglomerate the micropearls to obtain a precipitated silica sample in the form of a powder, before applying the method for determining the primary particle size by SAXS.

[0108] On the other hand, if the precipitated silica is in the form of granules, that is to say in the form of another highly aggregated particle, it is desirable to deagglomerate the granules, thereby obtaining a precipitated silica sample in the form of a powder, before applying the method for determining the primary particle size by SAXS and before applying the method for determining the CTAB surface area.

[0109] In both cases the same deagglomeration pretreatments are applied, one of which is detailed below.

[0110] A deagglomeration pretreatment for highly agglomerated particle shapes, especially precipitated silica in the form of micropearls or granules. Precipitated silica samples in the form of highly aggregated particles, especially granules or micropearls, were ground smoothly using a hand mortar and pestle to break down the aggregates and other lumps contained therein by manually applying smooth pressure and friction to the silica sample. The grinding was operated for a period of time sufficient for the sample to acquire a visually homogeneous consistency of a powder, the duration of which was generally several tens of seconds and generally did not exceed one minute.

[0111] To be clear, the above pretreatment should not be operated if the precipitated silica is in the form of a powder. Methods for determination of the BET surface area, methods for determination of the fineness rate by "Sedigraph", amount of aluminum WAl When applying the method for determining the CTAB surface area or the method for determining the moisture content (all such methods are as detailed below) to precipitated silicas, regardless of their form, the above pretreatment is possible but not necessary and therefore generally not applicable. When applying the method for determining the CTAB surface area to precipitated silicas in the form of micropearls, the above pretreatment is possible but not necessary and therefore generally not applicable.

[0112] Determination of CTAB surface area CTAB surface area (S CTAB ) values ​​were determined according to the internal method derived from standard NF ISO 5794-1, Appendix G. This method was based on the adsorption of CTAB (N-hexadecyl-N,N,N-trimethylammonium bromide) on the "external" surface of the silica.

[0113] In this method, CTAB was adsorbed onto silica under magnetic stirring. The silica and residual CTAB solution were then separated. Excess, unadsorbed CTAB was determined by back titration with sodium sulfosuccinate bis(2-ethylhexyl) (hereafter "AOT") using a titroprocessor, with the end point given by the turbidity maximum of the solution, determined using an optrode.

[0114] device Metrohm optrode connected to photometer 662 Metrohm (wavelength: 520 nm); Metrohm titrator: Titrino DMS 716; Metrohm titration software: Tiamo.

[0115] glass beakers (2000 mL); volumetric flasks (2000 mL); sealable glass bottles (1000 and 2000 mL); disposable beakers (100 mL); micropipettes (500 - 5000 µL); a magnetic stir bar with a 25 mm disk end for adsorption (Ref VWR 442-9431); a magnetic stir bar for titrations (straight); polycarbonate centrifuge tubes (at least 20 mL), centrifuge (capable of 10000 rpm); glass vials (30 mL); a thermobalance.

[0116] Preparation of solutions Preparation of CTAB solution at 5.5 g / L (buffered at about pH 9.6): In a 2000 mL beaker containing about 1000 mL of distilled water, at 25° C., 54.25 g of boric acid solution ([c]=4%), 2.60 g of KCl, 25.8 mL (±0.1 mL) of sodium hydroxide were added. The solution so obtained was stirred for 15 minutes, after which 11.00 g±0.01 g of CTAB powder (purity 99.9%, purchased from Merck) was added. After stirring, the solution was transferred to a 2000 mL volumetric flask kept at 25° C. and the volume was made up to 2000 mL with distilled water. The solution was transferred to a 2000 mL glass bottle. To avoid CTAB crystallization (occurs at 20° C.), the solution was stored at a temperature above 22° C.

[0117] Preparation of AOT solution: Approximately 1200 mL of distilled water in a 2000 mL beaker was heated to 35° C. under magnetic stirring. 3.7038 g of AOT (98% purity, purchased from Aldrich) was added. The solution was transferred to a 2000 mL volumetric flask and cooled to 25° C. The volume was made up to 2000 mL with distilled water and the solution was transferred to two 1000 mL glass bottles which were stored at 25° C. in the dark.

[0118] All equipment and solutions were stored at 25° C. during the analysis.

[0119] Procedures at the start and end of each experiment At the start of the experiment: The solution was stirred before use. The dosing apparatus was purged before use. At least 40 mL of AOT was passed through the apparatus to ensure it was healthy and all air bubbles were removed. At the end of the experiment: The dosing apparatus was purged to remove the AOT solution. Clean the optrode. Immerse the optrode in distilled water.

[0120] Determination of blank factor Fluctuations in the concentration of the AOT and CTAB solutions over time are corrected through the determination of a daily "blank factor", called the ratio R1=V1 / m1.

[0121] Accurately weigh out 4.9000 g ± 0.0100 g of 5.5 g / L CTAB solution (M1) into a 100 mL disposable beaker. Tare and add 23.0000 g ± 1.0000 g of distilled water (M1). WATER ) was added accurately. The solution was placed under stirring using a magnetic stirrer at 500 rpm on the dosing apparatus and the titration was started. The stirring speed should be strictly stable throughout the titration without generating too many air bubbles.

[0122] V1 is the end volume of AOT solution required to titrate ml of CTAB solution.

[0123] Perform R1 determinations at least in duplicate. If the standard deviation of R1=V1 / m1 exceeds 0.010, repeat the titration until the standard deviation is 0.010 or less. Calculate the daily ratio R1 as the average of duplicate or triplicate measurements. Note: The optrode should be washed with distilled water and dried with absorbent paper after each measurement.

[0124] Adsorption of CTAB on silica The moisture content (%H2O) for each silica sample was determined using a thermobalance (temperature: 160 °C) before the adsorption step as follows: tare the balance with an aluminum cup, weigh out approximately 2 g of silica, distribute the powder evenly on the cup, close the balance and note the percentage of moisture.

[0125] Accurately weigh 0.0100 g of silica (m0) into a 100 mL disposable beaker. 50.0000 mL + 1.0000 mL of CTAB stock solution (V0) was added. The total mass was recorded. The suspension was stirred for 40 min ± 1 min at 450 rpm using a magnetic stir bar with a disk end on a stir plate. After 40 min, the sample was removed from the stir plate.

[0126] 25-50 mL of the suspension was transferred to centrifuge tubes (volume depends on the size of the centrifuge tubes) and they were centrifuged at 25° C. for 35 minutes at a speed of 10000 rpm. After centrifugation, the tubes were slowly removed from the centrifuge without destabilizing the silica. 10-20 mL of the CTAB solution was transferred to glass vials, which were then stoppered and stored at 25° C.

[0127] Titration of CTAB solution Accurately weigh 4.0000 g ± 0.0100 g of CTAB solution of unknown concentration (m2) into a 100 mL disposable beaker.

[0128] Set the tare weight and weigh 19.4000g ± 1.0000g of water (M water The solution was placed on a dosing apparatus under stirring at 500 rpm and titration with the AOT solution was started.

[0129] V2 is the end volume of AOT required to titrate m2 of the CTAB solution.

[0130] CTAB surface area S CTAB is calculated as follows:

number

[0131] BET surface area determination BET surface area S BET was determined according to the Brunauer-Emmett-Teller method detailed in standard NF ISO 5794-1 Annex E (June 2010) with the following adjustment: the sample was pre-dried at 160°C ± 10°C and the partial pressure P / P used for the measurement 0 was in the range of 0.05 to 0.2.

[0132] Determination of particle size distribution and particle size by centrifugal sedimentation in a disc centrifuge using a centrifugal photosedimentometer (CPS) By centrifugal sedimentation in a disk centrifuge using a centrifugal photosedimentometer type "CPS DC 24000UHR" marketed by CPS Instruments. 50 , d 16 , d 84 , FWHM, and L d The instrument is equipped with operating software supplied with the device (operating software version 11g).

[0133] Instrumentation used: For the measurement requirements, the following materials and products were used: Ultrasonic equipment: 1500W generator type Sonics Vibracell VC1500 / VCX1500 with 19mm probe (Converter: CV154 + Booster (Part number: BHNVC21) + 19mm probe (Part number: 630-0208)).

[0134] Analytical balance with 0.1 mg accuracy (e.g. Mettler AE260); Syringes: 1.0 ml and 2.0 ml with 20 ga needle; 50 mL high profile glass beaker (SCHOTT DURAN: diameter 38 mm, height 78 mm); magnetic stirrer with 2 cm stirring bar; container for ice bath during sonication.

[0135] Chemicals: deionized water; ethanol 96%; sucrose 99%; dodecane, all from Merck; PVC reference standards from CPS Instrument Inc.; the peak maximum of the reference standards used should be between 200-600 nm (e.g., 237 nm).

[0136] Preparation of the disc centrifuge For the measurements the following parameters were set: For the calibration standard parameters the information of the PVC standard provided by the supplier was used.

[0137] [Table 1]

[0138] System Configuration The measurement wavelength was set to 405 nm. The following runtime option parameters were set:

[0139] [Table 2]

[0140] All other options in the software were left as set by the instrument manufacturer.

[0141] Preparation of the disc centrifuge Spin the centrifuge disks at 24000 rpm for 30 min. Prepare a density gradient of sucrose (CAS n° 57-50-1) as follows:

[0142] In a 50 mL beaker, prepare a 24% by weight solution of sucrose in water. In a 50 mL beaker, prepare an 8% by weight solution of sucrose in water. After homogenizing these two solutions separately, use a 2 mL syringe to take a sample from each solution and inject it into the rotating disc in the following order: Sample 1: 1.8 mL of 24 wt% solution Sample 2: 1.6 mL of 24 wt% solution + 0.2 mL of 8 wt% solution Sample 3: 1.4 mL of 24 wt% solution + 0.4 mL of 8 wt% solution Sample 4: 1.2 mL of 24 wt% solution + 0.6 mL of 8 wt% solution Sample 5: 1.0 mL of 24 wt% solution + 0.8 mL of 8 wt% solution Sample 6: 0.8 mL of 24 wt% solution + 1.0 mL of 8 wt% solution Sample 7: 0.6 mL of 24 wt% solution + 1.2 mL of 8 wt% solution Sample 8: 0.4 mL of 24 wt% solution + 1.4 mL of 8 wt% solution Sample 9: 0.2 mL of 24 wt% solution + 1.6 mL of 8 wt% solution Sample 10: 1.8 mL of 8 wt% solution.

[0143] Before each injection into the disk, the two solutions are homogenized in the syringe by adding about 0.2 mL of air and then by short manual stirring for a few seconds, without losing any liquid.

[0144] These injections, the total volume of which is 18 mL, aim to create a density gradient that is useful to eliminate certain instabilities that may appear during the injection of the samples to be measured. To protect the density gradient from evaporation, 1 mL of dodecane is added into the rotating disc using a 2 mL syringe. The disc is then left to rotate at 24000 rpm for 60 minutes before any first measurement.

[0145] Sample preparation 3.2 g of silica was weighed into a 50 mL tall-form glass beaker (SCHOTT DURAN: diameter 38 mm, height 78 mm) and 40 mL of deionized water was added to obtain an 8 wt% suspension of silica. The suspension was stirred with a magnetic stirrer (minimum 20 seconds) before placing the beaker in a crystallizing dish filled with ice and cold water. The magnetic stirrer was removed and the crystallizing dish was placed under an ultrasonic probe placed 1 cm from the bottom of the beaker. The ultrasonic probe was set to 56% of its maximum amplitude and activated for 8 minutes. At the end of the sonication, the beaker was placed back on the magnetic stirrer with a 2 cm magnetic stir bar stirring at a minimum of 500 rpm until after sample extraction.

[0146] The ultrasonic probe must be in good working order. The following inspections must be carried out and in case of unfavourable results a new probe should be used: visual inspection of the physical integrity of the end of the probe (roughness depth less than 2 mm measured with fine calipers); measured depth of the commercial silica Zeosil® 1165MP 50 should be 93 nm ± 3 nm.

[0147] analysis Before analyzing each sample, a calibration standard was recorded. In each case, 0.1 mL of a PVC standard was injected, provided by CPS Instruments, whose characteristics were entered in advance into the software. It is important to start the measurement in the software simultaneously with this first injection of the PVC standard. The instrument must be checked before injecting 100 μL of pre-sonicated sample by ensuring that the measurement is started simultaneously upon injection.

[0148] These injections were performed with two clean 1 mL syringes.

[0149] At the end of the measurement, when the time required to settle all particles of smaller diameter (configured in the software to be 0.02 μm) is reached, the ratio of each diameter class is obtained. The curve obtained is called the aggregate size distribution.

[0150] result d 50 , d 16 , d 84 and L d The values ​​of are based on the distribution plotted on a straight line. The integration of the particle size distribution function of the diameters makes it possible to obtain the "cumulative" distribution, i.e. the total mass of particles between the minimum diameter and the diameter of interest.

[0151] d 50 : 50% of the population by mass has a diameter less than or greater than this. d 50 is referred to as the median size, or diameter, of the silica particles.

[0152] d 84 : The diameter below which 84% of the particle's total mass is measured.

[0153] d 16 : The diameter below which 16% of the particle's total mass is measured.

[0154] L d :Equation:L d =(d 84 -d 16 ) / d 50 It is calculated according to:

[0155] FWHM: As explained herein above, it is calculated using the derivative of the cumulative distribution curve described above.

[0156] Determination of fines percentage by the "sedigraph" method. In this test, the ability to disperse silica is measured by particle size measurements (by sedimentation) carried out on silica suspensions previously deagglomerated by ultrasound. Deagglomeration (or dispersion) under ultrasound is implemented using a VIBRACELL BIOBLOCK sonifier (1500W) equipped with a probe with a diameter of 19 mm. Particle size measurements are carried out using a SEDIGRAPH particle sizer (sedimentation in a gravitational field + X-ray beam scanning).

[0157] 6.4 grams of silica are weighed in a tall beaker (volume equal to 100 mL) and supplemented to 80 grams by successively converting water, thus creating an 8% aqueous silica suspension, which is homogenized by magnetic stirring for 2 minutes. Deagglomeration (dispersion) under ultrasound is then carried out as follows: the probe is immersed over a length of 3 cm and the output power is adjusted to deliver 58 kJ to the suspension in 480 seconds. Particle size measurements are then carried out by means of a SEDIGRAPH particle sizer. Measurements are made between 85 μm and 0.3 μm with a density of 2.1 g / mL. The deagglomerated silica suspension, optionally pre-cooled, is then circulated in the particle size cell of the SEDIGRAPH. As soon as a size of 0.3 μm is reached, the analysis stops automatically (about 45 min). The fines fraction (τf), i.e. the proportion of particles (by weight) with a size smaller than 1 μm, is then calculated. The higher this fines fraction (τf), or the more particles have a size below 1 μm, the better the dispersibility of the silica.

[0158] It is understood that the ultrasonic probe must be in proper condition for use. To this end, the following checks can be made: (i) visual inspection of the physical integrity of the end of the probe (roughness depth less than 2 mm measured with fine calipers); and / or (ii) the measured τf of the commercial silica Zeosil® 1165MP, aged for at least 2 years, should be 97%. In case of negative results, the power output should be readjusted. If negative results persist, a new probe should be used.

[0159] Determination of primary particle size by SAXS 1) Principle of the method Small angle X-ray scattering (SAXS) consists of the deviation of an incident X-ray beam of wavelength λ through a sample in a cone shape with an angle of a few degrees. The scattering angle θ corresponds to a wave vector defined by the following relation:

number

[0160] Each scattering angle corresponds to a wave vector q defined in reciprocal space. This wave vector corresponds to a spatial scale defined in real space, which is equal to 2π / q. Thus, scattering at small angles characterizes large distances in the sample, and conversely, scattering at large angles characterizes small distances in the sample. The technique is sensitive to the way matter is distributed in space.

[0161] Basic references on this technology are provided below: [1] Small Angle Scattering of X rays, Guinier A., ​​Fournet G., (1955), Wiley, New 5 York. [2] Small Angle X Ray Scattering, Glatter O., Krattky O., (1982), Academic Press, New York. [3]Analysis of the Small-Angle Intensity Scattered by a Porous and Granular Medium,Spalla O.,Lyonnard S.,Testard F.,J.Appl.Cryst.(2003),36,338-347.10

[0162] The requirements for SAXS to characterize silica according to the following criteria are as follows: - a SAXS assembly operating in transmission geometry (i.e., the incident beam passing through the sample) with an incident wavelength between 0.5 and 2 Angstroms (Å); 0.015 Å, which allows characterizing distances in real space ranging from -420 to 20 Å -1 ~0.30Å -1 Wave vector interval q of - the assembly is verified on the q scale using suitable standards (for example silver behenate, octadecanol or any other compound giving fine SAXS lines included in the q interval above), a one-dimensional linear detector or preferably a two-dimensional one, - that the assembly must make it possible to measure the transmittance of the preparation, i.e. the ratio between the intensity transmitted by the sample and the incident intensity.

[0163] Such an assembly may be, for example, a laboratory assembly operating on a source of the type of X-ray tube or rotating anode, preferably using copper Kα radiation at 1.54 Å. The detector may be a CCD detector, an imaging plate or a gas detector. It may also be a SAXS mounted on a synchrotron. In the framework of this application, a CCD detector was used.

[0164] 2) Procedure The silica sample is analyzed in powdered solid form. The powder is placed between two transparent X-ray transmitting windows. Independently of this preparation, an empty cell with no silica inside is made with two transparent windows. The diffusion through the empty cell shall be recorded separately from the diffusion of silica. During this operation, called "background measurement", the scattering intensity is given from all external contributions to the silica, such as electronic background noise, diffusion from the transparent windows, residual divergence of the incident beam, etc.

[0165] These transparent windows must provide low background noise in front of the intensity scattered by the silica over the wavevector interval probed. They may be made of mica, Kapton or Mylar film, or preferably an adhesive Kapton film or Mylar with a thin layer of grease.

[0166] Prior to the actual SAXS acquisition of the silica, the quality of the preparation should be confirmed by a transmittance measurement of the silica-containing cell.

[0167] Therefore, the steps to be performed are:

[0168] 2.1) Elaboration of a cell consisting of two silica-free windows (empty cell).

[0169] 2.2) Preparation of a two-window cell containing a sample of silica powder inside. The amount of silica introduced must be less than 50 mg. The silica must form a layer less than 100 μm thick. Preference is given to obtaining a monolayer of silica particles placed on the window, which is easier to obtain with adhesive windows. The quality of the preparation is controlled by measurements of the transmittance (step 2.3)).

[0170] 2.3) Measurement of the transmittance of the empty cell and the silica cell. The R ratio is defined as follows: R = transmittance of silica cell / transmittance of empty cell To minimize the risk of multiple scattering while maintaining a satisfactory signal-to-noise ratio for large q, R should be between 0.85 and 1. If the R value is too low, the amount of silica visible to the beam must be reduced, if it is too high, more silica must be added.

[0171] 2.4) Acquisition of SAXS in an empty cell and a silica cell. The acquisition times are determined to allow a signal-to-noise ratio at large q. They are: q = 0, 12 Å -1In the immediate vicinity of , the fluctuation of the function F(q) defined below shall not exceed + / - 5% with respect to the value taken by the function F at that time.

[0172] 2.5) When a 2D detector was used, a radial grouping of each of the two 2D profiles was performed to obtain the scattering intensity as a function of the wave vector q. The determination of the scattering intensity must take into account the exposure time, the intensity of the incident beam, the transmittance of the sample, and the solid angle intercepted by the detector pixels. The determination of the wave vector must take into account the wavelength of the incident beam and the sample-to-detector distance.

[0173] 2.6) When using a one-dimensional detector, prior determination of scattering intensity and wave vector is to be made, but radial grouping is not anticipated.

[0174] 2.7) This gives two profiles that reduce the information to the variation of the scattered intensity as a function of the wave vector q: one profile for the empty cell and one profile for the silica cell.

[0175] 2.8) The intensity scattered by the empty cell is subtracted from the intensity scattered by the silica cell ("background" subtraction).

[0176] 2.9) The SAXS profile of silica has a monotonic decay that follows a regime close to the Porod law after “background” subtraction, i.e., q -4 The problem is that the intensity decreases very rapidly with the wave vector, following a law close to an exponential law of . This small deviation from the Porod law is best seen by expressing the data according to the so-called Krattky-Porod method, which is a problem of expressing F(q) as a function of q, which is: F(q) = I × q 4 where F represents the SAXS profile by the Krattky-Porod method, I represents the scattering intensity after "background" subtraction, and q represents the wave vector (Å -1 unit).

[0177] 2.10) When describing the profile in the Krattky-Porod representation, in some cases a maximum can be observed, which is associated with the presence of primary particles of roughly defined size. With low polydispersity the maximum is all the more pronounced. In the case of monodisperse primary particles a second or third oscillation is observed to the right of the maximum. The position of the maximum is related to the average size of the primary particles by the law 2π / q.

[0178] Two different determinations can be made, both of which provide information about the dimensions of the primary particles.

[0179] The first decision is I×q 4 =F(q) is based on the unit of the maximum value in 2π / q max For a single strip population of spheres, this distance does not correspond exactly to the diameter, but to 115% of the diameter (in Å). This application does not allow access to the size distribution, but to the average diameter, where the largest particles have a strong influence.

[0180] Another determination is the average size d ZS (Zimm-Schultz mean diameter). Therefore, I×q 4 The SAXS profile at =F(q) is modeled by a distribution of independent spheres (with different diameters) of the Zimm-Schultz type distribution.

[0181] The skilled artisan is familiar with the use of such distributions to fit the many distributions observed in various fields of chemistry. As references the following may in particular be cited: - J. Welch, VA Bloomfield, J. Pol. Sci., Polymer Physics Edition, vol. 11 (1973), titled "Fitting Polymer Distribution Data to a Schulz-Zimm Function" - HJ Angerman, G.ten Brinke, JJMSlot, The European Physical Journal B, 12, 397-404 (1999), entitled "Influence of polydispersity on the phase behavior of statistical multiblock copolymers with Schultz-Zimm block molecular weight distributions", and - LHHanus, HJPloehn, Langmuir, 15, 3091-3100 (1999), entitled "Conversion of Intensity-averaged Photon Correlation Spectroscopy Measurements to Number-Averaged Particle Size Distributions1.Theoretical Development".

[0182] This last paper concerns the determination of the average particle diameter of a distribution of particles, as is the case for the silica of the invention. The Zimm-Schultz type distribution function, as shown in Table 1 of this last paper, is evaluated, and the general formula for converting the intensity-average particle diameter and the polydispersity index into the mean and standard deviation of the Zimm-Schultz type distribution function can be found in Table 2 of this last paper.

[0183] The modeled SAXS profile is based on the well-known SAXS shape factors. Thus, for a single sphere with diameter d (d=2×r, where r is the radius of the sphere in Å), we have the following:

number

[0184] For a distribution of independent spheres with different diameters, the (total) scattering intensity I(q) after “background” subtraction at wave vector q is given by

number

number

[0185] Zimm-Schultz distribution function f(r)=f for independent spheres ZS (r) is generally represented by:

number

number

[0186] The modeled SAXS profile FZS(q) based on isolated spheres with a Zimm-Schultz type distribution according to the invention is therefore:

number

[0187] Therefore, the modeled profile requires two inputs to fit: 1) the mean diameter d ZS and 2) polydispersity index i p (through the parameters t and a). In addition, the multiplicative constant k is added to the F ZS Used to adjust the profile.

[0188] These inputs are the wave vector intervals [q min ,q max ] to best fit F(q) = I.q4 (SAXS profile in Krattky-Porod representation) (for the avoidance of doubt, Å -1 q expressed in units min andq maxと where F(q) denotes the lower and upper bounds of the wavevector interval, respectively), can be determined using conventional numerical tools or on a trial-and-error basis. The best fit is when the modeled and experimental data match as closely as possible in the interval surrounding the maximum (i.e., the square of the experimental value of F(q) and the modeled value F ZS (q) squared is the smallest.

[0189] In practice, the Zimm-Schultz distribution is min ,r max For a given wave vector, each discretized Zimm Schultz class is given its form factor [I(q,r), SF)] and its weight f ZS (r) contributes to the modeled SAXS profile through:

number

[0190] For convenience, the calculations may be performed after introducing the above formula into a spreadsheet.

[0191] Since this model does not take into account cohesion, but rather the presence of correlation between the spheres, it also does not take into account consolidation, i.e. the presence of additional material welding the primary particles together.

[0192] 2.11) From the Zimm-Schultz distribution model, we obtain the mean diameter d ZS The SAXS particle size was determined to be (Zimm-Schultz mean diameter), which is midway between the mean diameter by number and the mean diameter by volume extracted from the same Zimm-Schultz distribution model.

[0193] Amount of aluminum W Al Decision The weight of aluminum based on the weight of SiO2 was measured using XRF wavelength dispersive X-ray fluorescence spectroscopy using a WDXRF Panalytical instrument. Sample analysis was performed under helium in a 4 cm diameter cell with silica, specifically silica powder, contained in a cell covered by a thin Prolene film (4 μm Chemplex®), ranging from 0.1 to 3.0% (by weight) Al / SiO2.

[0194] Al and Si fluorescence were measured using the following parameters: Al Kα angle 2θ = 144.9468° (20 s), background signal angle 2θ = -1.2030° (4 s), Si Kα angle 2θ = 109.1152° (10 s), tube power 4 kW (32 kV, 125 mA), PE002 crystal and 550 μm collimator, gas flux detector.

[0195] The weight of aluminum in precipitated silica samples containing more than 3.0% Al / SiO2 was determined by ICP OES (Inductively Coupled Plasma Optical Emission Spectroscopy). The precipitated silica samples were degassed in hydrofluoric acid (e.g., about 0.2-0.3 g of precipitated silica and 1 mL of hydrofluoric acid at a concentration of 40%). A clear solution was obtained, which was diluted in 5% aqueous nitric acid according to the expected Al concentration. The intensity measured at the Al specific wavelength (396.152 nm) was compared with a calibration curve ranging from 0.05 to 2.00 mg / L obtained using aluminum standards (four standards at 0.10, 0.20, 1.00 and 2.00 mg / L) under similar analytical conditions. The weight content of aluminum in the precipitated silica samples was calculated using the dilution factor. The weight of aluminum based on the weight of SiO of the precipitated silica sample was then calculated from the weight content of aluminum and the weight content of water in the precipitated silica sample, taking into account that the precipitated silica sample consisted essentially of SiO (typically from about 95 to about 99% by weight) and water (typically from about 5 to about 1% by weight).

[0196] Moisture determination The moisture content of silica samples, especially those containing more than 3.0% Al / SiO2, was determined according to ISO 787-2. The silica volatile fraction (herein referred to as moisture for simplicity) was determined after drying at 105° C. for 2 hours. The drying loss consisted primarily of moisture.

[0197] 10 g of powdered silica, spherical silica (Micropearl) or granular silica were weighed to 0.1 mg (weighing material E) and placed in a dry weighing bottle with a ground glass cover (diameter 8 cm, height 3 cm). The samples were dried in a drying cabinet with the lid open at 105±2°C for 2 hours. The weighing bottle was then closed and cooled to room temperature in a desiccator containing silica gel as desiccant. The weighed portion A was weighed. The moisture was determined in percentage according to [(E (in g)-A (in g))*100%] / (E (in g)). EXAMPLES

[0198] Examples 1 to 14: Synthesis of Silica Example 1 (according to the present invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na2SO4 (solid) were introduced. The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium.

[0199] A sodium silicate solution (SiO2 / Na2O weight ratio=3.47; SiO2 concentration=19.9% ​​by weight) with a flow rate of 103.2 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 102.9 g / min were simultaneously dosed over a period of 2.9 minutes. The same sodium silicate solution was used throughout the process. Sulfuric acid was then introduced into the reactor to reach a pH value of 4.25. A sodium silicate solution with a flow rate of 105 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 123.3 g / min were then simultaneously dosed over a period of 12.2 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.25. At the end of this step, a sodium silicate solution with a flow rate of 104.3 g / min and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 10.05 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.25.

[0200] The acid charge was then stopped while the addition of sodium silicate was maintained at a flow rate of 118.5 g / min over a period of 2.4 minutes until the reaction medium reached a pH value of 8.00.

[0201] Sodium silicate and 96 wt.% sulfuric acid solutions were then simultaneously dosed over a period of 18.05 minutes at a flow rate of 164.3 g / min. The flow rate of the 96 wt.% sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0202] At the end of the simultaneous addition, the pH of the reaction medium was 4.6 containing 96% by weight of sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.

[0203] The reaction slurry was filtered and washed in a filter press. It was mechanically and chemically disintegrated by adding aluminum metal Al in the form of an aluminate solution of about 0.30% by weight ([Al]: 11.6% by weight, [Na2O]: 19.9% ​​by weight) relative to the weight of SiO2, aiming at an Al / SiO2 weight ratio of about 0.33% by weight (it is understood that about 0.03% by weight of Al comes from the silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 6.3. The obtained slurry was dried by a nozzle spray dryer to obtain precipitated silica S1.

[0204] The characteristics of the precipitated silica S1 are reported in Table I.

[0205] Example 2 (according to the present invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na2SO4 (solid) were introduced. The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium.

[0206] A sodium silicate solution (SiO2 / Na2O weight ratio=3.46; SiO2 concentration=19.33% by weight) with a flow rate of 104.5 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 113.6 g / min were simultaneously dosed over a period of 3.8 minutes. The same sodium silicate solution was used throughout the process. Sulfuric acid was then introduced into the reactor to reach a pH value of 4.08. A sodium silicate solution with a flow rate of 108.3 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 124.4 g / min were then simultaneously dosed over a period of 11.35 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.08. At the end of this step, a sodium silicate solution with a flow rate of 108.1 g / min and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 5.05 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.08.

[0207] The acid charge was then stopped while the addition of sodium silicate was maintained at a flow rate of 121.9 g / min over a period of 2.8 minutes until the reaction medium reached a pH value of 8.00.

[0208] Sodium silicate and 96 wt.% sulfuric acid solutions were then simultaneously dosed over a period of 21.71 minutes at a flow rate of 169.1 g / min. The flow rate of the 96 wt.% sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0209] At the end of the simultaneous addition, the pH of the reaction medium was 4.33 containing 96% by weight of sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.

[0210] The reaction slurry was filtered and washed in a filter press. It was mechanically and chemically disintegrated by adding aluminum metal Al in the form of an aluminate solution of about 0.30% by weight ([Al]: 11.6% by weight, [Na2O]: 19.9% ​​by weight) relative to the weight of SiO2, aiming at an Al / SiO2 weight ratio of about 0.33% by weight (it is understood that about 0.03% by weight of Al comes from the silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 6.3. The obtained slurry was dried by a nozzle spray dryer to obtain precipitated silica S2.

[0211] The properties of the precipitated silica S2 are reported in Table I.

[0212] Example 3 (according to the present invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na2SO4 (solid) were introduced. The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium.

[0213] A sodium silicate solution (SiO2 / Na2O weight ratio=3.46; SiO2 concentration=19.33% by weight) with a flow rate of 106.2 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 112.8 g / min were simultaneously dosed over a period of 4.7 minutes. The same sodium silicate solution was used throughout the process. Sulfuric acid was then introduced into the reactor to reach a pH value of 4.43. A sodium silicate solution with a flow rate of 107.8 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 122.3 g / min were then simultaneously dosed over a period of 10.55 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.43. At the end of this step, a sodium silicate solution with a flow rate of 108.5 g / min and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 9.95 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.43.

[0214] The acid charge was then stopped while the addition of sodium silicate was maintained at a flow rate of 125.9 g / min for 3 minutes until the reaction medium reached a pH value of 8.00.

[0215] Sodium silicate and 96 wt.% sulfuric acid solutions were then simultaneously dosed over a period of 18.10 minutes at a flow rate of 169.1 g / min. The flow rate of the 96 wt.% sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0216] At the end of the simultaneous addition, the pH of the reaction medium was 4.45 containing 96% by weight of sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.

[0217] The reaction slurry was filtered and washed in a filter press. It was mechanically and chemically disintegrated by adding aluminum metal Al in the form of an aluminate solution of about 0.30% by weight ([Al]: 11.6% by weight, [Na2O]: 19.9% ​​by weight) relative to the weight of SiO2, aiming at an Al / SiO2 weight ratio of about 0.33% by weight (it is understood that about 0.03% by weight of Al comes from the silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 6.3. The obtained slurry was dried by a nozzle spray dryer to obtain precipitated silica S3.

[0218] The properties of the precipitated silica S3 are reported in Table I.

[0219] Example 4 (according to the present invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na2SO4 (solid) were introduced. The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium.

[0220] A sodium silicate solution (SiO2 / Na2O weight ratio=3.46; SiO2 concentration=19.33% by weight) with a flow rate of 105.6 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 110.8 g / min were simultaneously dosed over a period of 4.71 minutes. The same sodium silicate solution was used throughout the process. Sulfuric acid was then introduced into the reactor to reach a pH value of 4.08. A sodium silicate solution with a flow rate of 105.6 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 124.3 g / min were then simultaneously dosed over a period of 10.45 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.08. At the end of this step, a sodium silicate solution with a flow rate of 108.5 g / min and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 10 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.08.

[0221] The acid charge was then stopped while the addition of sodium silicate was maintained at a flow rate of 124.4 g / min over a period of 3.45 minutes until the reaction medium reached a pH value of 8.00.

[0222] Sodium silicate and 96 wt.% sulfuric acid solutions were then simultaneously dosed over a period of 18.07 minutes at a flow rate of 169.3 g / min. The flow rate of the 96 wt.% sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0223] At the end of the simultaneous addition, the pH of the reaction medium was 4.6 containing 96% by weight of sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.

[0224] The reaction slurry was filtered and washed in a filter press. It was mechanically and chemically disintegrated by adding aluminum metal Al in the form of an aluminate solution of about 0.30% by weight ([Al]: 11.6% by weight, [Na2O]: 19.9% ​​by weight) relative to the weight of SiO2, aiming at an Al / SiO2 weight ratio of about 0.33% by weight (it is understood that about 0.03% by weight of Al comes from the silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 6.3. The obtained slurry was dried by a nozzle spray dryer to obtain precipitated silica S4.

[0225] The properties of the precipitated silica S4 are reported in Table I.

[0226] Example 5 (according to the present invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na2SO4 (solid) were introduced. The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium.

[0227] A sodium silicate solution (SiO2 / Na2O weight ratio=3.46; SiO2 concentration=19.33% by weight) with a flow rate of 104.1 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 109.4 g / min were simultaneously dosed over a period of 4.05 minutes. The same sodium silicate solution was used throughout the process. Sulfuric acid was then introduced into the reactor to reach a pH value of 3.8. A sodium silicate solution with a flow rate of 108.3 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 126.3 g / min were then simultaneously dosed over a period of 11.12 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 3.8. At the end of this step, a sodium silicate solution with a flow rate of 108.1 g / min and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 10 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 3.8.

[0228] The acid charge was then stopped while the addition of sodium silicate was maintained at a flow rate of 123.4 g / min over a period of 2.7 minutes until the reaction medium reached a pH value of 8.00.

[0229] Sodium silicate and 96 wt.% sulfuric acid solutions were then simultaneously dosed over a period of 18.07 minutes at a flow rate of 169.4 g / min. The flow rate of the 96 wt.% sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0230] At the end of the simultaneous addition, the pH of the reaction medium was 4.53 containing 96% by weight of sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.

[0231] The reaction slurry was filtered and washed in a filter press. It was mechanically and chemically disintegrated by adding aluminum metal Al in the form of about 0.30 wt.% aluminate solution ([Al]: 11.6 wt.%, [Na2O]: 19.9 wt.%) relative to the weight of SiO2, aiming at an Al / SiO2 weight ratio of about 0.33 wt.% (it is understood that about 0.03 wt.% Al comes from the silicate solution). The flow rate of the 7.7 wt.% sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 6.3. The obtained slurry was dried by a nozzle spray dryer to obtain precipitated silica S5.

[0232] The properties of the precipitated silica S5 are reported in Table I.

[0233] Example 6 (according to the present invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na2SO4 (solid) were introduced. The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium.

[0234] A sodium silicate solution (SiO2 / Na2O weight ratio=3.46; SiO2 concentration=19.33% by weight) with a flow rate of 105.8 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 107.6 g / min were simultaneously dosed over a period of 3.75 minutes. The same sodium silicate solution was used throughout the process. Sulfuric acid was then introduced into the reactor to reach a pH value of 4.43. A sodium silicate solution with a flow rate of 108.08 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 122.9 g / min were then simultaneously dosed over a period of 11.4 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.43. At the end of this step, a sodium silicate solution with a flow rate of 107.8 g / min and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 5 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.43.

[0235] The acid charge was then stopped while the addition of sodium silicate was maintained at a flow rate of 120.5 g / min for 2.1 minutes until the reaction medium reached a pH value of 8.00.

[0236] Sodium silicate and 96 wt.% sulfuric acid solutions were then simultaneously dosed over a period of 21.7 minutes at a flow rate of 169.4 g / min. The flow rate of the 96 wt.% sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0237] At the end of the simultaneous addition, the pH of the reaction medium was 4.6 containing 96% by weight of sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.

[0238] The reaction slurry was filtered and washed in a filter press. It was mechanically and chemically disintegrated by adding aluminum metal Al in the form of about 0.30 wt.% aluminate solution ([Al]: 11.6 wt.%, [Na2O]: 19.9 wt.%) relative to the weight of SiO2, aiming at an Al / SiO2 weight ratio of about 0.33 wt.% (it is understood that about 0.03 wt.% Al comes from the silicate solution). The flow rate of the 7.7 wt.% sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 6.3. The obtained slurry was dried by a nozzle spray dryer to obtain precipitated silica S6.

[0239] The properties of the precipitated silica S6 are reported in Table I.

[0240] Comparative Example 7 A 25 L stainless steel reactor was charged with 15.2 L of normal water and 356 g of Na2SO4 (solid). The resulting solution was stirred and heated to reach 92°C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium. Sulfuric acid (concentration: 7.7% by weight) was charged to the reaction vessel until a pH value of 4.43 was reached.

[0241] A sodium silicate solution (SiO2 / Na2O weight ratio=3.46; SiO2 concentration=19.33% by weight) with a flow rate of 88.8 g / min was dosed into the reaction vessel over a period of 45 seconds. The same sodium silicate solution was used throughout the process. Sulfuric acid was then introduced into the reactor to reach a pH value of 4.43. A sodium silicate solution with a flow rate of 111.8 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 123.6 g / min were then simultaneously dosed over a period of 14.97 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.42. At the end of this step, a sodium silicate solution with a flow rate of 109.3 g / min and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 9.85 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.42.

[0242] The acid charge was stopped while the addition of sodium silicate was maintained at a flow rate of 118.9 g / min over a period of 2.4 minutes until the reaction medium reached a pH value of 8.00.

[0243] Sodium silicate and 96 wt.% sulfuric acid solutions were then simultaneously dosed over a period of 18.22 minutes at a flow rate of 166.3 g / min. The flow rate of the 96 wt.% sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0244] At the end of the simultaneous addition, the pH of the reaction medium was 4.6 containing 96% by weight of sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.

[0245] The reaction slurry was filtered and washed in a filter press. It was mechanically and chemically disintegrated by adding aluminum metal Al in the form of about 0.30 wt.% aluminate solution ([Al]: 11.6 wt.%, [Na2O]: 19.9 wt.%) relative to the weight of SiO2, aiming at an Al / SiO2 weight ratio of about 0.33 wt.% (it is understood that about 0.03 wt.% Al comes from the silicate solution). The flow rate of the 7.7 wt.% sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 6.3. The obtained slurry was dried by a nozzle spray dryer to obtain precipitated silica CS7.

[0246] The properties of the precipitated silica CS7 ​​are reported in the table.

[0247] Comparative Example 8 (based on International Publication No. 2018 / 202752) A 2500 L stainless steel reactor was charged with 1126 L of water and 29.7 kg of Na2SO4 (solid). The resulting solution was stirred and then heated until it reached 92°C. All reactions were carried out at this temperature. A 96% by weight sulfuric acid solution was charged into the reactor until a pH value of 3.9 was reached. A sodium silicate solution (SiO2 / Na2O ratio = 3.45, SiO2 concentration = 19.3% by weight) was charged into the reactor at a flow rate of 420 L / h over 51 seconds. The same sodium silicate solution was used throughout the process. Then, a sodium silicate solution at a flow rate of 445 L / h, water at a flow rate of 575 L / h and a 96% by weight sulfuric acid solution were simultaneously charged over a period of 14.9 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.3. At the end of this step, a sodium silicate solution at a flow rate of 445 L / h and a 96% by weight sulfuric acid solution were simultaneously charged over a period of 9.45 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 4.3.

[0248] The acid charge was then stopped while the addition of sodium silicate was placed at a flow rate of 579 L / h until the reaction medium reached a pH value of 8.00.

[0249] Sodium silicate and 96% by weight sulfuric acid solutions were then simultaneously dosed over a period of 3 minutes at a flow rate of 708 L / h. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0250] At the same time, a calculated sodium solution with a flow rate of 706 l / h, a sodium aluminate solution (Al: 12.2 wt. %, Na2O: 19.4 wt. %) and a 96% sulfuric acid solution with a flow rate of 47.6 kg / h were added over a period of 14.8 minutes, the sodium aluminate solution being added in such an amount as to aim for an Al / SiO2 weight ratio of about 1.40 wt. % (understood to be about 0.03 wt. % Al coming from the silicate solution).

[0251] The flow rate of the 96% sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.0.

[0252] At the end of this simultaneous addition, the pH of the reaction medium was 4.4 containing 96% by weight of sulfuric acid. Water was then charged, the temperature was reduced to 85° C. and the reaction mixture was allowed to mature for 5 minutes. A slurry was obtained.

[0253] The reaction slurry was filtered and washed with a filter press to give a precipitated silica cake of 23% solids by weight.

[0254] The resulting silica cake was then subjected to a liquefaction process in a continuously vigorously stirred reactor. Then, 200 g of 7.7% sulfuric acid solution was added to the mixture to adjust the pH. The pH value of the liquefied cake was 6.0, and it had a solid content of 23% by weight.

[0255] The obtained slurry was dried by a nozzle type spray dryer to obtain precipitated silica Micropearl CS8.

[0256] The properties of the precipitated silica CS8 are reported in Table I.

[0257] Comparative Example 9 (based on International Publication No. 2009 / 112458) A 25 L stainless steel reactor was charged with 9.26 L of tap water, 136.6 g of Na2SO4 (solid) and 4756 g of sodium silicate solution (SiO2 / Na2O weight ratio = 3.46, SiO2 concentration = 19.95 wt%). The solution was stirred and heated to reach 92.5°C. The entire reaction was carried out at this temperature with stirring to maintain a homogenous reaction medium.

[0258] A 7.7% by weight sulfuric acid solution was dosed over 17 minutes with a flow rate of 110.7 g / min. The flow rate of the 7.7% by weight sulfuric acid solution was then adjusted to 321.0 g / min in order to reach the pH of the reaction medium, which was set at a value of 8.0.

[0259] A sodium silicate solution with a flow rate of 95.3 g / min and a 7.7 wt. % sulfuric acid solution were then simultaneously dosed over a period of 10 minutes. The flow rate of the 7.7 wt. % sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0260] At the end of this step, the pH of the reaction medium was brought to a value of 4.05 using 7.7% by weight sulfuric acid over a period of 8 minutes.

[0261] A sodium silicate solution with a flow rate of 64.3 g / min and a 7.7% by weight sulfuric acid solution were then simultaneously dosed over a period of 28 minutes. The flow rate of the 7.7% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 4.05.

[0262] The acid charge was then stopped while the addition of sodium silicate was maintained at a flow rate of 29 g / min over 4.6 minutes until the reaction medium reached a pH value of 5.2. The reaction mixture was aged for 5 minutes. A slurry was obtained.

[0263] The slurry was filtered and washed with a filter press to obtain a precipitated silica cake with a solid content of 20% by weight. The obtained silica cake was then subjected to a liquefaction process in a continuous vigorously stirred reactor by adding sodium aluminate solution ([Al]: 11.6% by weight-[Na2O]: 19.9% ​​by weight) and sulfuric acid solution at 7.7% by weight to adjust the pH. The sodium aluminate solution was added in an amount to aim for an Al / SiO2 weight ratio of about 0.33% by weight (understood to be about 0.03% by weight Al from the silicate solution). The pH value of the liquefied cake was 6.4, and the cake had a solid content of 20%. The obtained slurry was dried by a nozzle spray dryer to obtain precipitated silica powder.

[0264] The granulation process was then carried out. 150 g of silica powder was used per batch, which were fed into a granulator (Alexanderwerk, granulator WP 120 Pharma). Silica granules were formed by using an air gap of 3 mm, an oil pressure of 20 bar and a roller speed of 3-5 rpm. The granulator speed was fixed at 108 rpm, and a sieving of 1-2.5 mm was achieved. The duration of the granulation process was about 15 minutes per batch. Precipitated silica granules CS9 were thus obtained.

[0265] The properties of the precipitated silica CS9 are reported in Table I.

[0266] Example 10 (according to the invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na2SO4 (solid) were introduced. The resulting solution was stirred and heated to reach 92°C. The entire reaction was carried out at this temperature with stirring in order to maintain a homogeneous reaction medium. A sodium silicate solution (SiO2 / Na2O weight ratio = 3.46, SiO2 concentration = 19.33 wt%) with a flow rate of 102.7 g / min and a 7.7 wt% sulfuric acid solution with a flow rate of 28.3 g / min were simultaneously dosed over a period of 3.74 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 8.0. This step was named "AS0".

[0267] After this step, a 7.7% by weight sulfuric acid solution was added to the reactor to reach a pH value of 4.2. A sodium silicate solution with a flow rate of 105.1 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 122.3 g / min were then simultaneously added over 11.55 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 4.2. At the end of this step, a sodium silicate solution with a flow rate of 104.9 g / min and a 96% by weight sulfuric acid solution were simultaneously added over 4.85 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.2. After 2.15 minutes, a gel point was observed in this step. The silicate added after the gel point was equal to 13% of the total silicate added from the beginning of the reaction.

[0268] The acid charge was then stopped while the addition of sodium silicate was maintained at a flow rate of 146.8 g / min for 2.00 minutes until the reaction medium reached a pH value of 8.00.

[0269] The sodium silicate solution and the 96% by weight sulfuric acid solution were then simultaneously dosed over a period of 21.73 minutes at a flow rate of 163.3 g / min. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0270] At the end of this step, the pH of the reaction medium was brought to a value of 4.8 with 96% by weight of sulfate. The reaction mixture was aged for 5 minutes. A slurry was obtained.

[0271] The slurry was filtered and washed with a filter press to obtain a precipitated silica cake with a solid content of 20% by weight. The obtained silica cake was then subjected to a liquefaction process in a continuous vigorously stirred reactor by adding sodium aluminate solution ([Al]: 11.6% by weight-[Na2O]: 19.9% ​​by weight) and sulfuric acid solution at 7.7% by weight to adjust the pH. The sodium aluminate solution was added in an amount to aim for an Al / SiO2 weight ratio of about 0.18% by weight (understood to be about 0.03% by weight Al from the silicate solution). The pH value of the liquefied cake was 6.4 and the solid content was 20%. The obtained slurry was dried by a nozzle spray dryer to obtain precipitated silica powder.

[0272] The granulation step was then carried out. 150 g of silica powder was used per batch and they were fed into a granulator (Alexanderwerk, granulator WP 120 Pharma). Silica granules were formed by using an air gap of 3 mm, an oil pressure of 20 bar and a roller speed of 3-5 rpm. The granulator speed was fixed at 108 rpm and a sieving of 1-2.5 mm was achieved. The duration of the granulation step was about 15 minutes per batch. Precipitated silica granules S10 were thus obtained.

[0273] The properties of precipitated silica S10 are reported in Table I.

[0274] Example 11 (according to the invention) Into a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na2SO4 (solid) were introduced. The resulting solution was stirred and heated to reach 92°C. The entire reaction was carried out at this temperature with stirring in order to maintain a homogeneous reaction medium. A sodium silicate solution (SiO2 / Na2O weight ratio = 3.46, SiO2 concentration = 19.33 wt%) with a flow rate of 102.7 g / min and a 7.7 wt% sulfuric acid solution with a flow rate of 28.3 g / min were simultaneously dosed over a period of 3.74 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 8.0. This step is named AS0. After this step, a 7.7 wt% sulfuric acid solution was dosed into the reactor to reach a pH value of 4.2. A sodium silicate solution with a flow rate of 105.1 g / min and a 7.7 wt% sulfuric acid solution with a flow rate of 122.3 g / min were then simultaneously dosed over a period of 11.55 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set at a value of 4.2. At the end of this step, a sodium silicate solution with a flow rate of 104.9 g / min and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 4.85 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.2. After 2.15 minutes, a gel point was observed in this step. The silicate added after the gel point was equal to 13% of the total silicate added from the beginning of the reaction.

[0275] The acid charge was then stopped while the addition of sodium silicate was maintained at a flow rate of 146.8 g / min for 2.00 minutes until the reaction medium reached a pH value of 8.00.

[0276] The sodium silicate solution and the 96% by weight sulfuric acid solution were then simultaneously dosed over a period of 21.73 minutes at a flow rate of 163.3 g / min. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0277] At the end of this step, the pH of the reaction medium was brought to a value of 4.8 with 96% by weight of sulfate. The reaction mixture was aged for 5 minutes. A slurry was obtained.

[0278] The slurry was filtered and washed with a filter press to obtain a precipitated silica cake with a solid content of 20% by weight. The obtained silica cake was then subjected to a liquefaction process in a continuous vigorously stirred reactor by adding sodium aluminate solution ([Al]: 11.6% by weight - [Na2O]: 19.9% ​​by weight) and 7.7% (by weight) sulfuric acid solution to adjust the pH. The sodium aluminate solution was added in such an amount as to aim for an Al / SiO2 weight ratio of about 1.1-1.2% by weight. The pH value of the liquefied cake was 6.4 and the solid content was 20%. The obtained slurry was dried by a nozzle type spray dryer to obtain precipitated silica powder.

[0279] The granulation step was then carried out. 150 g of silica powder was used per batch and they were fed into a granulator (Alexanderwerk, granulator WP 120 Pharma). Silica granules were formed by using an air gap of 3 mm, an oil pressure of 20 bar and a roller speed of 3-5 rpm. The granulator speed was fixed at 108 rpm and a sieving of 1-2.5 mm was achieved. The duration of the granulation step was about 15 minutes per batch. Precipitated silica granules S11 were thus obtained.

[0280] The properties of the precipitated silica S11 are reported in Table I.

[0281] Example 12 (according to the invention) A 2500 L stainless steel reactor was charged with 1124 L of water and 29.8 kg of Na2SO4 (solid). The resulting solution was stirred and then heated until it reached 92° C. All reactions were carried out at this temperature.

[0282] A sodium silicate solution (SiO2 / Na2O ratio=3.45, SiO2 concentration=18.8% by weight) with a flow rate of 436 L / h, water with a flow rate of 582 L / h and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 6.2 minutes. The flow rate of the sulfuric acid was adjusted so as to maintain the pH of the reaction medium at a value of 8.2.

[0283] The introduction of the sodium silicate solution was then stopped until the reaction medium reached a pH value of 3.8.

[0284] Then, a sodium silicate solution with a flow rate of 445 L / h, water with a flow rate of 575 L / h and a 96% by weight sulfuric acid solution were simultaneously dosed over 7.1 minutes. The flow rate of the sulfuric acid was adjusted so as to maintain the pH of the reaction medium at a value of 3.8. At the end of this step, a sodium silicate solution with a flow rate of 445 L / h and a 96% by weight sulfuric acid solution were simultaneously dosed over 6.1 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 3.8.

[0285] The gel point was about 11 minutes. During all these steps of simultaneous addition of sodium silicate solution and acid, the amount of sodium silicate added after the gel point was equal to 53% of the total amount added during this step.

[0286] The acid charge was then stopped while the addition of sodium silicate was placed at a flow rate of 622 L / h until the reaction medium reached a pH value of 8.00.

[0287] Then, a sodium silicate solution with a flow rate of 706 L / h and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 22.4 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0288] At the end of this simultaneous addition, the pH of the reaction medium was 4.9 containing 96% by weight of sulfuric acid. Water was then charged, the temperature was reduced to 85° C. and the reaction mixture was allowed to mature for 5 minutes. A slurry was obtained.

[0289] Each reaction slurry was filtered and washed with a filter press to yield a precipitated silica cake of 23% solids by weight.

[0290] The silica cake obtained was then subjected to a liquefaction step in a continuous vigorously stirred reactor by adding sodium aluminate solution ([Al]: 12.5 wt% - [Na2O]: 19.5 wt%) and sulfuric acid solution at 7.7 wt% to adjust the pH. The sodium aluminate solution was added in such an amount as to aim for an Al / SiO2 weight ratio of about 0.33 wt% (understood to be about 0.03 wt% Al coming from the silicate solution). The pH value of the liquefied cake was 6.3 and the solid content was 23 wt%.

[0291] The obtained slurry was dried by a nozzle type spray dryer to obtain precipitated silica Micropearl S12.

[0292] The properties of the precipitated silica S12 are reported in Table I.

[0293] Example 13 (according to the invention) A 2500 L stainless steel reactor was charged with 1126 L of water and 29.8 kg of Na2SO4 (solid). The resulting solution was stirred and then heated until it reached 92° C. All reactions were carried out at this temperature.

[0294] A sodium silicate solution (SiO2 / Na2O ratio=3.45; SiO2 concentration=19.3% by weight) with a flow rate of 434 L / h, water with a flow rate of 586 L / h and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 3.7 minutes. The flow rate of the sulfuric acid was adjusted so as to maintain the pH of the reaction medium at a value of 8.4.

[0295] The introduction of the sodium silicate solution was then stopped until the reaction medium reached a pH value of 3.9.

[0296] Then, a sodium silicate solution with a flow rate of 445 L / h, water with a flow rate of 567 L / h and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 9.8 minutes. The flow rate of the sulfuric acid was adjusted so as to maintain the pH of the reaction medium at a value of 3.9. At the end of this step, a sodium silicate solution with a flow rate of 445 L / h and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 5.9 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 3.9.

[0297] The gel point was about 15.3 minutes. During all of these steps of simultaneous addition of sodium silicate and acid, the amount of sodium silicate added after the gel point was equal to 29% of the total amount added during this step.

[0298] The acid charge was then stopped while the addition of sodium silicate was placed at a flow rate of 618 L / h until the reaction medium reached a pH value of 8.00.

[0299] The sodium silicate solution and the 96% by weight sulfuric acid solution were then simultaneously dosed over a period of 22.4 minutes at a flow rate of 705 L / h. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0300] At the end of this simultaneous addition, the pH of the reaction medium was 4.8 containing 96% by weight of sulfuric acid. Water was then charged, the temperature was reduced to 85° C. and the reaction mixture was allowed to mature for 5 minutes. A slurry was obtained.

[0301] Each reaction slurry was filtered and washed with a filter press to yield a precipitated silica cake of 23% solids by weight.

[0302] The resulting silica cake was then subjected to a liquefaction step in a continuous vigorously stirred reactor by adding sodium aluminate solution ([Al]: 12.5 wt% - [Na2O]: 19.5 wt%) and 7.7 wt% sulfuric acid solution to adjust the pH. The sodium aluminate solution was added in such an amount as to aim for an Al / SiO2 weight ratio of about 0.50 wt% (understood to be about 0.03 wt% Al coming from the silicate solution). The pH value of the liquefied cake was 6.4 and the solid content was 23 wt%.

[0303] The obtained slurry was dried by a nozzle type spray dryer to obtain precipitated silica Micropearl S13.

[0304] The properties of the precipitated silica S13 are reported in Table I.

[0305] Example 14 (according to the invention) A 2500 L stainless steel reactor was charged with 1124 L of water and 29.7 kg of Na2SO4 (solid). The resulting solution was stirred and then heated until it reached 92° C. All reactions were carried out at this temperature.

[0306] A sodium silicate solution (SiO2 / Na2O ratio=3.45; SiO2 concentration=19.3% by weight) with a flow rate of 445 L / h, water with a flow rate of 575 L / h and a 96% by weight sulfuric acid solution were simultaneously dosed over a period of 6.2 minutes. The flow rate of the sulfuric acid was adjusted so as to maintain the pH of the reaction medium at a value of 8.2.

[0307] The introduction of the sodium silicate solution was then stopped until the reaction medium reached a pH value of 4.0.

[0308] Then, a sodium silicate solution with a flow rate of 445 L / h, water with a flow rate of 575 L / h and a 96% by weight sulfuric acid solution were simultaneously dosed over 7.1 minutes. The flow rate of the sulfuric acid was adjusted so as to maintain the pH of the reaction medium at a value of 3.85. At the end of this step, a sodium silicate solution with a flow rate of 445 L / h and a 96% by weight sulfuric acid solution were simultaneously dosed over 6 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 3.85.

[0309] The acid charge was then stopped while the addition of sodium silicate was placed at a flow rate of 610 L / h until the reaction medium reached a pH value of 8.00.

[0310] The sodium silicate solution and the 96% by weight sulfuric acid solution were then simultaneously dosed over a period of 22.4 minutes at a flow rate of 705 L / h. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.

[0311] At the end of this simultaneous addition, the pH of the reaction medium was 4.80 containing 96% by weight of sulfuric acid. Water was then charged, the temperature was reduced to 85° C. and the reaction mixture was allowed to mature for 5 minutes. A slurry was obtained.

[0312] Each reaction slurry was filtered and washed with a filter press to yield a precipitated silica cake of 23% solids by weight.

[0313] The silica cake obtained was then subjected to a liquefaction step in a continuous vigorously stirred reactor by adding sodium aluminate solution ([Al]: 12.5 wt% - [Na2O]: 19.5 wt%) and sulfuric acid solution at 7.7 wt% to adjust the pH. The sodium aluminate solution was added in such an amount as to aim for an Al / SiO2 weight ratio of about 1.20 wt% (understood to be about 0.55 wt% Al coming from the silicate solution). The pH value of the liquefied cake was 6.4 and the solid content was 23 wt%.

[0314] The obtained slurry was dried by a nozzle type spray dryer to obtain precipitated silica Micropearl S14.

[0315] The properties of the precipitated silica S14 are reported in Table I.

[0316] [Table 3]

[0317] Example 15: Use of Silica in Elastomer Compositions material The silica S2 according to the invention was evaluated in an SBR / BR model tire tread in comparison with a silica obtained according to WO 03 / 016215 in the name of the Applicant (i.e. the silica CS7 ​​described in Comparative Example 7 above). The compositions, expressed in parts by weight per 100 parts of elastomer (phr), are given in Table II below.

[0318] [Table 4]

[0319] (1) Oil-extended SBR, Buna VSL4526-2HM from Lanxess with 45% vinyl units; 26% styrene units; Tg of -30°C, 37.5 phr TDAE (2)BR: Butyl rubber, Buna CB 25 from Lanxess (3) TESPT: Bis[3-(triethoxysilyl)propyl]tetrasulfide, TESPT Luvomaxx from Lehmann&Voss&Co. (4) SYLVATRAXX 4101 Hydrocarbon Resin from Arizona Chemical (5) 6PPD: N-(1,3-dimethylbutyl)-N-phenyl-para-phenylenediamine, Santoflex 6-PPD from Flexsys (6) DPG: Diphenylguanidine, Rhenogran DPG-80 from RheinChemie (7) CBS: N-cyclohexyl-2-benzothiazole sulfenamide, Rhenogran CBS-80 from RheinChemie

[0320] Process for preparing rubber composition The preparation of the rubber composition was carried out in two successive preparation stages: a first stage of high temperature thermomechanical processing, followed by a second stage of mechanical processing at a temperature below 110° C. to introduce the vulcanization system. The first stage was carried out using a mixing device of the Brabender brand internal mixer type (volume of 380 mL).

[0321] In the first pass of the first stage, the elastomer and reinforcing filler (introduced in portions) were mixed with the coupling agent, plasticizer, stearic acid, 6-PPD, DPG and ZnO, the duration was 4 minutes 30 seconds and the drop temperature was about 160°C.

[0322] After cooling the mixture (to a temperature below 100 ° C), the vulcanization system was added during the second stage, which was carried out in an open mill preheated to 50 ° C. 20 cuts were made to ensure good homogeneity of the vulcanization system in the compound. The duration of this stage was 2 to 6 minutes. Each final mixture was subsequently calendered into plaques of thickness 2 to 3 mm.

[0323] Properties of the vulcanizate The measurements were carried out after vulcanization at 150°C for 50 minutes.

[0324] After crosslinking, the Z value was measured according to ISO 11345, according to the method described by S. Otto et al. in Kautschuk Gummi Kunststoffe, 58 Jahrgang, NR 7-8 / 2005.

[0325] The percentage of "undispersed area" is calculated using a camera observing the surface of the sample with light incidence at 30°. The bright spots are associated with charges and aggregates, the dark spots with the rubber matrix. Digital processing converts the image into a black and white image, which allows the percentage of "undispersed area" to be determined, as described by S. Otto in the abovementioned publication. The higher the Z value, the better the distribution of the charges within the elastomer matrix (a Z value of 100 corresponds to perfect distribution, a Z value of 0 corresponds to very poor distribution).

[0326] The calculation of the Z value is based on the percentage of the area where the charge is not distributed according to the formula: Z=100-(percentage of undistributed area) / 0.35, as measured by a DisperGrader® 1000 instrument with operating mode and operating software DisperData from Dynisco.

[0327] Uniaxial tensile tests were carried out on H2 type test specimens in an Instron 5564 machine at a speed of 500 mm / min according to the instructions of standard NF ISO 37. The x% modulus, which corresponds to the stress measured at x% tensile strain, is expressed in MPa. The tensile strength is expressed in MPa and the elongation at break is expressed in MPa.

[0328] The reinforcement index (RI), equal to the ratio of the modulus at 300% strain to the modulus at 100% strain, was determined.

[0329] The loss factor (tan δ) and the amplitude of the elastic modulus in dynamic shear (ΔG') were measured for the vulcanized specimen (parallel hexahedral specimen: cross-sectional area 8 mm 2 The measurements were recorded at a temperature of 40° C. and a height of 7 mm. The samples were subjected to a double alternating sinusoidal shear strain at a temperature of 40° C. and a frequency of 10 Hz. The strain amplitude sweep process was performed following a forward-return cycle going outwards from 0.1% to 50% and then back from 50% to 0.1%. The values ​​reported in Table III below are obtained from the return strain amplitude scan and relate to the maximum value of the loss factor (tan δmax). The measurements were performed on a Metravib DMA+1000.

[0330] All results are summarized in Table III below.

[0331] [Table 5]

[0332] The silica according to the invention exhibits excellent dispersibility, intermediate reinforcement index, tensile strength and elongation at break while maintaining a low tan δmax, which allows a better wear resistance / rolling resistance compromise to be found.

[0333] Example 16: Use of Silica in Elastomer Compositions material Silicas S5, S10, S11, S12, S13 and S14 according to the invention - two silicas commercially available from SOLVAY SA, namely ZEOSIL® 1165 silica (simply Z1165MP) and ZEOSIL® Premium 200MP silica (simply ZP200MP), and - It was evaluated in an SBR / BR compound in comparison with two silicas according to the teachings of various prior art patent applications, namely silicas CS8 and CS9.

[0334] Three formulations were used, as detailed in Tables IV, V and VI below: The amounts of ingredients included in the test compositions were expressed as parts by weight per 100 parts of elastomer (phr).

[0335] [Table 6]

[0336] (1) Oil-extended SBR, Buna VSL4526-2HM from Lanxess with 45% vinyl units; 26% styrene units; Tg of -30°C, 37.5 phr TDAE (2)BR: Butyl rubber, Buna CB 25 from Lanxess (3) TESPD: Bis[3-(triethoxysilyl)propyl]disulfide, TESPD Luvomaxx from Lehmann&Voss&Co. (4) SYLVATRAXX 4101 Hydrocarbon Resin from Arizona Chemical (5) 6PPD: N-(1,3-dimethylbutyl)-N-phenyl-para-phenylenediamine, Santoflex 6-PPD from Flexsys (6) DPG: Diphenylguanidine, Rhenogran DPG-80 from RheinChemie (7) CBS: N-cyclohexyl-2-benzothiazole sulfenamide, Rhenogran CBS-80 from RheinChemie

[0337] [Table 7]

[0338] (1) Oil-extended SBR, Buna VSL4526-2HM from Lanxess with 45% vinyl units; 26% styrene units; Tg of -30°C, 37.5 phr TDAE (2)BR: Butyl rubber, Buna CB 25 from Lanxess (3) TESPT: Bis[3-(triethoxysilyl)propyl]tetrasulfide, TESPT Luvomaxx from Lehmann&Voss&Co. (4) SYLVATRAXX 4101 Hydrocarbon Resin from Arizona Chemical (5) 6PPD: N-(1,3-dimethylbutyl)-N-phenyl-para-phenylenediamine, Santoflex 6-PPD from Flexsys (6) DPG: Diphenylguanidine, Rhenogran DPG-80 from RheinChemie (7) CBS: N-cyclohexyl-2-benzothiazole sulfenamide, Rhenogran CBS-80 from RheinChemie

[0339] [Table 8]

[0340] (1) Oil-extended SBR, Buna VSL4526-2HM from Lanxess with 45% vinyl units; 26% styrene units; Tg of -30°C, TDA of 37.5 phr (2)BR: Butyl rubber, Buna CB 25 from Lanxess (3) TESPT: Bis[3-(triethoxysilyl)propyl]tetrasulfide, TESPT Luvomaxx from Lehmann&Voss&Co. (4) SYLVATRAXX 4101 Hydrocarbon Resin from Arizona Chemical (5) 6PPD: N-(1,3-dimethylbutyl)-N-phenyl-para-phenylenediamine, Santoflex 6-PPD from Flexsys (6) DPG: Diphenylguanidine, Rhenogran DPG-80 from RheinChemie (7) CBS: N-cyclohexyl-2-benzothiazole sulfenamide, Rhenogran CBS-80 from RheinChemie

[0341] Process for preparing rubber composition The rubber composition of this Example 16 was prepared as detailed in Example 15, except for the vulcanization conditions (see "Vulcanizate Properties" herein below).

[0342] Properties of the vulcanizate The vulcanization conditions applied in this Example 16 were: - for the compounds of table IV, vulcanization at 160°C for 40 minutes; For the compounds of Tables V and VI, vulcanization was at 150° C. for 50 minutes.

[0343] The Z index, tensile strength, elongation at break, ΔG′ and tan δmax were also determined as detailed in Example 15.

[0344] The tear resistance was determined as follows.

[0345] To measure the tear resistance, uniaxial tensile tests were carried out on an Instron 5564 machine at a speed of 500 mm / min using test specimens of type C, according to the teachings of standard ASTM D624. The tear resistance (=tear strength) was expressed in N / mm.

[0346] [Table 9]

[0347] The silicas S10, S11 and S12 according to the invention showed excellent dispersion (Z index).Compared to the commercial silica grade Zeosil® 1165MP, the silicas according to the invention made it possible to significantly reduce the energy dissipation (ΔG', tan δmax) while retaining good reinforcement: better macrodispersion (Z index), similar elongation at break and slightly lower tensile strength.

[0348] Silicas from the prior art, so-called CS8 and CS9, offered low energy dissipation but poor dispersion (Z index) and a reduction in tensile strength and elongation at break.

[0349] Overall, the silica according to the invention allows for a better wear / energy dissipation compromise.

[0350] [Table 10]

[0351] In comparison with the commercially available Zeosil® Premium 200MP silica, the silicas S13 and S5 according to the invention showed better dispersibility.

[0352] [Table 11]

[0353] Compared to the commercially available Zeosil® 1165MP, the silica S14 according to the invention allows a reduction in the energy dissipation (tan δmax) while maintaining a high dispersibility (Z index) and a high tear resistance.

Claims

1. 4. Precipitated silica, comprising: - 40 to 525 m 2 / g range of CTAB surface area; - primary particles having an average size, determined by SAXS, of less than 15 nm; - a fines fraction τf, which is the proportion (by weight) of particles with a size of less than 1 μm, after deagglomeration by ultrasound, which is at least 91%; and For a given value of the CTAB surface area, the parameter FWHM satisfies the relationship (I): |FWHM|>-0.16×|CTAB|+130(I) Particle size distribution measured by centrifugal sedimentation using CPS as defined by Precipitated silica, characterized by:

2. 50 to 300 m 2 / g, preferably 70 to 300m 2 / g, more preferably from 80 to 270 m 2 / g, or alternatively from 120 to 275 m 2 2. The precipitated silica of claim 1 having a CTAB surface area of ​​up to 1 / g.

3. 120m 2 / g and 230m 2 3. The precipitated silica of claim 2 having a CTAB surface area of ​​less than 1 / g.

4. 4. The precipitate of claim 1, 2 or 3 having a FWHM in the range of 100 to 250.

5. The following formula: |d 50 |>-0.81×|CTAB|+263 (II) The present invention is characterized by the following: 50 5. Precipitated silica according to claim 1, having the formula:

6. d of 110 nm to 240 nm, preferably 130 to 220 nm 50 6. Precipitated silica according to claim 1, having the formula:

7. The following formula: |d 84 |<2.81×|FWHM|+35 (III) The present invention is characterized by the following: 84 7. Precipitated silica according to claim 1, having the formula:

8. 200 to 550 nm, preferably 250 to 500 nm 84 8. The precipitated silica of claim 7, having

9. 9. Precipitated silica according to any one of the preceding claims, containing at least one element selected from Al, Ga, B, Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Fe, Co, Mg, Ca or Zn.

10. 10. Precipitated silica according to any one of the preceding claims, having a fines fraction τf of at least 92%, preferably at least 94%.

11. 11. Precipitated silica according to claim 10, having a fines fraction of at least 95%, in some cases at least 97%.

12. A precipitated silica according to any one of claims 1 to 11, in the form of a powder.

13. 12. Precipitated silica according to claim 1, in the form of micropearls.

14. A precipitated silica according to any one of claims 1 to 11, in the form of granules.

15. 1. A process for preparing precipitated silica, the process comprising: (i) providing a starting solution having a pH of from 2.00 to 5.50; (ii) adding silicate and acid simultaneously to the starting solution so as to maintain the pH of the reaction medium in the range of from 2.00 to 5.50; (iii) stopping the addition of the acid and the silicate and adding a base to the reaction medium to increase the pH of the reaction medium to a value of from 7.00 to 10.00; (iv) simultaneously adding a silicate and an acid to the reaction medium such that the pH of the reaction medium is maintained in the range of from 7.00 to 10.00; (v) continuing the addition of the acid to the reaction medium while stopping the addition of the silicate to allow the pH of the reaction medium to reach less than 6.00 to obtain a suspension of precipitated silica; The step (i) comprises the steps of: (ia) finally preparing an aqueous medium containing electrolyte as an initial stock; (ib) adding silicate and acid simultaneously to the aqueous medium such that the pH of the aqueous medium is maintained in the range of from 7.00 to 10.00, the amount of silicate added to the aqueous medium being 1-10% of the total amount of silicate required for the reaction, preferably 5-9% of the total amount of silicate required for the reaction; (ic) stopping the addition of silicate while continuing the addition of the acid to the aqueous medium obtained in step (ib) to provide the starting solution having a pH of from 2.00 to 5.50; A method comprising:

16. 16. The method of claim 15, wherein during step (ii) a gel point is reached, dilute acid is used until said gel point is reached, and concentrated acid is used after said gel point is reached.

17. 17. The method according to claim 15 or 16, wherein a gel point is reached during step (ii) and the amount of silicate added in step (ii) after said gel point is reached is between 5% and 55% of the total amount of silicate added in step (ii), preferably between 10% and 50% and more preferably between 15% and 45% of the total amount of silicate added in step (ii).

18. 18. The process according to any one of claims 15 to 17, wherein the amount of silicate added to the reaction medium during step (iv) is at least 45% of the total amount of silicate required for the reaction.

19. A method according to any one of claims 15 to 18, wherein the precipitated silica is a precipitated silica according to any one of claims 1 to 14.

20. 15. Use of the precipitated silica according to any one of claims 1 to 14 as a catalyst, catalyst support, absorbent for active materials (particularly as a carrier for liquids used in foods, in particular for vitamins (vitamin E or choline chloride)), viscosity modifier, anti-blocking or anti-caking agent, as an additive for toothpaste, concrete or paper, in the manufacture of insulation materials or in the preparation of resorcinol-formaldehyde / silica composites.

21. Use of the precipitated silica according to any one of claims 1 to 14 for the preparation of a filled polymer composition.

22. A composition comprising a precipitated silica according to any one of claims 1 to 14 and at least one polymer.

23. The precipitated silica is present in an amount W of less than 0.50 wt.%, preferably less than 0.45 wt.%, typically at least 0.01 and less than 0.50 wt.%. Al 23. The composition of claim 22, containing aluminum at

24. 24. The composition of claim 23, wherein the at least one polymer is one or more elastomers.

25. 25. Use of a composition according to claim 23 or 24 for the manufacture of a part of a tire.

26. 26. The use according to claim 25, wherein the tire component is a tire tread.

27. A tire component comprising the composition of claim 23 or 24.

28. 30. The component of claim 27, which is a tire tread.

29. A tire comprising a component according to claim 27 or 28.

30. 30. An article, generally a vehicle, comprising a tire according to claim 29.

31. 23. Use of the composition of claim 22 for the manufacture of a finished article other than any part of a tire, other than any tire, and other than any article including a tire.

32. 32. The use according to claim 31 , wherein the finished product is selected from the group consisting of footwear soles, floor coverings, engineering components, seals, pipes, coating materials, cables, supports, separators and belts.

33. 23. A finished article other than any component of a tire, other than any tire, and other than any article including a tire, said finished article consisting of or including at least one component consisting of the composition of claim 22.

34. 34. The finished product of claim 33, selected from the group consisting of footwear soles, floor coverings, engineering components, seals, pipes, coating materials, cables, supports, separators, and belts.

35. 23. Use of the composition according to claim 22 in footwear soles, floor coverings, gas barriers, flame retardant materials, engineering components such as rollers for cableways, seals for household appliances, seals for liquid or gas pipes, brake system seals, pipes (plastic), coating materials (especially cable coating materials), cables, engine supports, battery separators, conveyor belts, transmission belts.